In situ copper ion exchange in pre-exchanged copper zeolite materials.
An improved method for producing copper-containing zeolite catalysts using a specific aqueous mixture enhances NOx conversion activity, addressing the limitations of existing technologies by achieving high catalytic performance across varying temperatures.
Patent Information
- Application Number
- JP2021523584
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2018-10-30
- Filing Date
- 2019-10-30
- Publication Date
- 2024-12-20
- Estimated Expiration
- 2039-10-30
AI Technical Summary
Existing methods for producing copper-containing zeolite catalysts do not achieve optimal catalytic activity, particularly in terms of NOx conversion, both at low and high temperatures.
A method involving the use of a specific aqueous mixture containing a copper-containing zeolite material, alumina, silica, titania, zirconia, and ceria, with a non-zeolitic acidic material, applied to a substrate and calcined, enhancing the catalytic performance of the catalyst.
The method results in catalysts with improved NOx conversion activity across a range of temperatures, surpassing the performance of conventional liquid-phase ion exchange methods.
Smart Images

Figure 0007603200000007 
Figure 0007603200000008 
Figure 0007603200000009
Abstract
Description
[Technical field]
[0001] The present invention relates to a method for producing a catalyst comprising a zeolitic material containing copper, a catalyst comprising a zeolitic material containing copper obtained or obtainable by said method, an exhaust gas treatment system comprising said catalyst, an aqueous mixture and a method for its preparation, and a zeolitic material having framework type CHA and containing copper. [Background technology]
[0002] Regarding the ion exchange of zeolitic materials with copper and / or iron, a liquid phase ion exchange method is known, and such a method is disclosed in US8293199B2. Furthermore, WO2018 / 101718A1 discloses a different method for preparing a catalyst comprising a CHA zeolitic material containing copper ions. The method comprises mixing H-CHA, a copper precursor, Zr-acetate and deionized water. The slurry is further ground, coated on a substrate, dried and calcined. The resulting catalyst comprises Cu-exchanged CHA. This in-situ ion exchange method can improve the high temperature performance of the catalyst comprising the ion-exchanged catalyst as in US8293199B2 compared to the catalyst comprising copper that has been ion-exchanged by a liquid phase ion exchange method. However, there remains a need for further improved methods for preparing catalysts comprising zeolitic materials containing copper, and catalysts comprising said zeolitic materials that exhibit improved catalytic activity, such as NOx conversion. [Prior art documents] [Patent documents]
[0003] [Patent Document 1] US8293199B2 [Patent Document 2] WO2018 / 101718A1 Summary of the Invention [Problem to be solved by the invention]
[0004] It was therefore an object of the present invention to provide an improved method for producing catalysts comprising copper-containing zeolitic materials that exhibit high catalytic activity, e.g., NOx conversion.
[0005] Surprisingly, it has been found that the process of the present invention makes it possible to obtain catalysts comprising copper-containing zeolitic materials that achieve high catalytic activity, e.g., improved NOx conversion, at both low and high temperatures. [Means for solving the problem]
[0006] I. Methods for Producing Catalysts Containing Copper-Containing Zeolitic Materials The present invention thus relates to a method for producing a catalyst comprising a copper-containing zeolitic material, the method comprising the steps of: (i) preparing an aqueous mixture comprising water, a copper-containing zeolitic material, a source of copper other than a copper-containing zeolitic material, and a non-zeolitic acidic material selected from the group consisting of alumina, silica, titania, zirconia, ceria, mixed oxides comprising one or more of Al, Si, Ti, Zr and Ce, and mixtures of two or more of these; (ii) disposing the mixture from step (i) on a surface of an interior wall of a substrate having an inlet end, an outlet end, a substrate axial length extending from said inlet end to said outlet end, and a plurality of passages extending through the substrate and defined by the interior wall of the substrate, and optionally drying the substrate on which the mixture is disposed; (iii) calcining the substrate obtained in step (ii) Includes. [Brief description of the drawings]
[0007] [Figure 1] FIG. 1 shows the NOx conversion at 20 ppm NH3 slip at various temperatures for aged (hydrothermal aging at 800° C.) Example 1, Comparative Examples 1 and 2 catalysts. [Diagram 2]FIG. 2 shows the NOx conversion at 20 ppm NH3 slip at various temperatures for aged (hydrothermal aging at 850° C.) catalysts of Example 1, Comparative Examples 1 and 2. [Diagram 3] FIG. 3 shows the NOx conversion of the aged catalysts of Examples 5 and 6 at various temperatures. [Figure 4] FIG. 4 shows the NOx conversion at 20 ppm NH3 slip for the aged catalysts of Examples 5 and 6 at various temperatures. [Diagram 5] FIG. 5 shows the ammonia storage capacity of the aged catalysts of Examples 5 and 6 at various temperatures. [Figure 6] FIG. 6 shows the TOT-bound DRIFTS of Example 8, the starting material of Example 8, and Comparative Example 4. [Figure 7] FIG. 7 shows a peak fitting analysis (deconvolution diagram) using the peak areas under the first absorption peak and under the second absorption peak of Example 8. [Figure 8] FIG. 8 shows the maximum NOx conversion at various temperatures for aged (hydrothermal aging at 800° C.) catalysts of Comparative Example 6 and Examples 13.1-13.3. [Figure 9] FIG. 9 shows the NOx conversion at 235° C. for aged (hydrothermal aging at 800° C.) catalysts of Comparative Example 6 and Examples 13.1-13.3 with various CuO contents. [Figure 10] FIG. 10 shows the maximum NOx conversion at various temperatures for the aged (hydrothermally aged at 800° C.) Example 2 catalyst. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0008] For the aqueous mixture prepared in step (i), the zeolite material containing copper contained therein is ABW, ACO, AEI, AEL, AEN, AET, AFG, AFI, AFN, AFO, AFR, AFS, AFT, AFV, AFX, AFY, AHT, ANA, APC, APD, AST, ASV, ATN, ATO, ATS, ATT, ATV, AVL, AWO, AWW, BCT, BEA, BEC, BIK, BOF, BOG, BOZ, BPH, BRE, BSV, CAN, CAS, CDO, CFI, CGF, CGS, CHA, -CHI, -CLO, CON, CSV, CZP, DAC, DDR, DFO, DFT, DOH, DON, EAB, EDI, EEI, EMT, EON, EPI, ERI, ESV, ETR, EUO, * -EWT, EZT, FAR, FAU, FER, FRA, GIS, GIU, GME, GON, GOO, HEU, IFO, IFR, -IFU, IFW, IFY, IHW, IMF, IRN, IRR, -IRY, ISV, ITE, ITG, ITH, * -ITN, ITR, ITT, -ITV, ITW, IWR, IWS, IWV, IWW, JBW, JNT, JOZ, JRY, JSN, JSR, JST, JSW, KFI, LAU, LEV, LIO, -LIT, LOS, LOV, LTA, LTF, LTJ, LTL, LTN, MAR, MAZ, MEI, MEL, MEP, MER, MFI, MFS, MON, MOR, MOZ, * MRE, MSE, MSO, MTF, MTN, MTT, MTW, MVY, MWF, MWW, NAB, NAT, NES, NON, NPO, NPT, NSI, OBW, OFF, OKO, OSI, OSO, OWE, -PAR, PAU, PCR, PHI, PON, POS, PSI, PUN, RHO, -RON, RRO, RSN, RTE, RTH, RUT, RWR, RWY, SAF, SAO, SAS, SAT, SAV, SBE, SBN, SBS, SBT, SEW, SFE, SFF, SFG, SFH, SFN, SFO, SFS, * SFV, SFW, SGT, SIV, SOD, SOF, SOS, SSF, * -SSO, SSY, STF, STI, *It is preferred that the zeolitic material containing copper contained in the aqueous mixture prepared in step (i) has a framework type selected from the group consisting of STO, STT, STW, -SVR, SVV, SZR, TER, THO, TOL, TON, TSC, TUN, UEI, UFI, UOS, UOV, UOZ, USI, UTL, UWY, VET, VFI, VNI, VSV, WEI, -WEN, YUG, ZON, mixtures of two or more of these, and mixed types of two or more of these, more preferably a framework type selected from the group consisting of CHA, AEI, RTH, LEV, DDR, KFI, ERI, AFX, mixtures of two or more of these, and mixed types of two or more of these, more preferably a framework type selected from the group consisting of CHA, AEI, RTH, AFX, mixtures of two or more of these, and mixed types of two or more of these, more preferably a framework type selected from the group consisting of CHA and AEI. It is more preferred that the zeolitic material containing copper contained in the aqueous mixture prepared in step (i) has a framework type CHA.
[0009] It is preferable that 95 to 100 mass %, more preferably 98 to 100 mass %, more preferably 99 to 100 mass % of the framework structure of the zeolite material is composed of Si, Al and O, and in the framework structure, the molar ratio of Si to Al, calculated as molar SiO2:Al2O3, is more preferably in the range of 2:1 to 50:1, more preferably in the range of 5:1 to 45:1, more preferably in the range of 10:1 to 35:1, more preferably in the range of 16:1 to 28:1. It is more preferable that the copper-containing zeolite material contained in the aqueous mixture prepared in step (i) has framework type CHA, and the molar ratio of Si to Al, calculated as molar SiO2:Al2O3, is in the range of 2:1 to 50:1, more preferably in the range of 5:1 to 45:1, more preferably in the range of 10:1 to 35:1, more preferably in the range of 16:1 to 28:1, more preferably in the range of 16:1 to 19:1, or more preferably in the range of 23:1 to 27:1.
[0010] It is preferred that the zeolitic material, more preferably having framework CHA, contained in the aqueous mixture prepared in step (i) has an average crystallite size, as determined by scanning electron microscopy, of at least 0.1 micrometer, more preferably in the range of 0.1 to 3.0 micrometer, more preferably in the range of 0.3 to 1.5 micrometer, more preferably in the range of 0.4 to 1.0 micrometer.
[0011] The zeolitic material contained in the aqueous mixture prepared in step (i) is in the range of 400 to 650 ml, determined as described in Reference Example 1 herein. 2 / g, preferably 550 to 620 m 2 It is preferred that the carbon black has a BET specific surface area in the range of 1 / g.
[0012] Regarding the amount of copper contained in the zeolitic material contained in the aqueous mixture prepared in step (i), the amount of copper, calculated as CuO, is preferably in the range of 0.05 to 3.5 mass%, more preferably in the range of 0.1 to 3 mass%, more preferably in the range of 0.2 to 2 mass%, more preferably in the range of 0.5 to 1.75 mass%, more preferably in the range of 1 to 1.75 mass%, or more preferably in the range of 1.9 to 2.5 mass%, based on the mass of the zeolitic material contained in the aqueous mixture prepared in step (i).
[0013] For the source of copper other than the copper-containing zeolitic material contained in the aqueous mixture prepared in step (i), it is preferred that said source of copper is selected from the group consisting of copper acetate, copper nitrate, copper sulfate, copper formate, copper oxide, and mixtures of two or more thereof, more preferably selected from the group consisting of copper acetate, copper oxide, and mixtures thereof, more preferably copper oxide, more preferably CuO.
[0014] It is preferred that the aqueous mixture prepared in step (i) contains a copper source other than the copper-containing zeolitic material in an amount, calculated as CuO, in the range of 0.1 to 14 mass %, preferably in the range of 0.5 to 12 mass %, more preferably in the range of 1 to 10 mass %, more preferably in the range of 1.5 to 5.0 mass %, more preferably in the range of 1.5 to 4.5 mass %, based on the mass of the zeolitic material contained in the aqueous mixture prepared in step (i).It is more preferred that the aqueous mixture prepared in step (i) contains a copper source other than the copper-containing zeolitic material in an amount, calculated as CuO, in the range of 2.0 to 4.0 mass %, based on the mass of the zeolitic material contained in the aqueous mixture prepared in step (i).
[0015] Thus, the present invention preferably relates to a method for preparing a catalyst comprising a copper-containing zeolitic material, the method comprising the steps of: (i) preparing an aqueous mixture comprising water, a copper-containing zeolitic material, a source of copper other than the copper-containing zeolitic material, and a non-zeolitic acidic material selected from the group consisting of alumina, silica, titania, zirconia, ceria, mixed oxides comprising one or more of Al, Si, Ti, Zr and Ce, and mixtures of two or more of these, wherein the zeolitic material has a framework type selected from the group consisting of CHA, AEI, RTH, LEV, DDR, KFI, ERI, AFX, mixtures of two or more of these, and mixtures of two or more of these, more preferably a framework type selected from the group consisting of CHA, AEI, RTH, AFX, mixtures of two or more of these, and mixtures of two or more of these, more preferably a framework type selected from the group consisting of CHA and AEI, more preferably having framework type CHA; and the source of copper other than the copper-containing zeolitic material contained in the aqueous mixture prepared in step (i) is selected from the group consisting of copper acetate, copper oxide, mixtures thereof, more preferably copper oxide, more preferably CuO, (ii) disposing the mixture from step (i) on a surface of an interior wall of a substrate having an inlet end, an outlet end, a substrate axial length extending from said inlet end to said outlet end, and a plurality of passages extending through the substrate and defined by the interior wall of the substrate, and optionally drying the substrate on which the mixture is disposed; (iii) calcining the substrate obtained in step (ii) Includes.
[0016] In the present invention, the non-zeolitic acidic material contained in the aqueous mixture prepared in step (i) is preferably selected from the group consisting of alumina, silica, titania, mixed oxides containing one or more of Al, Si, and Ti, and mixtures of two or more of these, more preferably selected from the group consisting of alumina, silica, mixed oxides containing one or more of Al and Si, and mixtures of two or more of these, more preferably a mixture of alumina and silica. It is more preferable that 80 to 99 mass %, more preferably 85 to 98 mass %, more preferably 90 to 98 mass % of the mixture of alumina and silica is made of alumina, and more preferably 1 to 20 mass %, more preferably 2 to 15 mass %, more preferably 2 to 10 mass % of the mixture of alumina and silica is made of silica.
[0017] It is preferred that the aqueous mixture prepared in step (i) comprises the non-zeolitic acidic material in an amount in the range of 2 to 20% by weight, more preferably in the range of 5 to 15% by weight, more preferably in the range of 7 to 13% by weight, based on the weight of the zeolitic material contained in the aqueous mixture prepared in step (i).
[0018] The non-zeolitic acidic material contained in the aqueous mixture prepared in step (i) preferably has a Dv90 in the range of 0.5 to 10 micrometers, preferably in the range of 2 to 8 micrometers, more preferably in the range of 4 to 6 micrometers, where Dv90 is determined as described in Reference Example 3 herein.
[0019] Alternatively, it is preferred that the non-zeolitic acidic material contained in the aqueous mixture prepared in step (i) has a Dv90 in the range of 12 to 30 micrometers, preferably in the range of 13 to 25 micrometers, more preferably in the range of 15 to 20 micrometers, more preferably in the range of 17 to 19 micrometers, where Dv90 is determined as described in Reference Example 3 herein.
[0020] Preferably, in the aqueous mixture prepared in step (i), 10 to 90% by mass of the aqueous mixture is made up of water, more preferably 40 to 85% by mass, and more preferably 55 to 80% by mass.
[0021] For the aqueous mixture prepared in step (i), it is preferred that the aqueous mixture further comprises a precursor of the acidic component, and the precursor is more preferably one or more of an aluminum salt, a silicon salt, a zirconium salt, and a titanium salt, more preferably one or more of a zirconium salt and an aluminum salt, more preferably a zirconium salt, more preferably zirconium acetate. In the aqueous mixture prepared in step (i), it is more preferred that the amount of the precursor calculated as an oxide, more preferably alumina, silica, zirconia, or titania, more preferably the amount of the zirconium salt calculated as ZrO2, is in the range of 1 to 10% by mass, more preferably in the range of 2 to 8% by mass, more preferably in the range of 3 to 7% by mass, based on the mass of the zeolite material contained in the aqueous mixture prepared in step (i).
[0022] It is preferred that the aqueous mixture prepared in step (i) further comprises one or more additional non-zeolitic acidic materials selected from the group consisting of alumina, silica, titania, zirconia and ceria, mixed oxides comprising one or more of Al, Si, Ti, Zr and Ce, and mixtures of two or more of these.
[0023] For the aqueous mixture prepared in step (i), it is preferred that the aqueous mixture further comprises one or more acids, more preferably two acids, more preferably two organic acids, more preferably tartaric acid and acetic acid, more preferably in an amount in the range of 0.1 to 2 mass %, more preferably in the range of 0.2 to 1.5 mass %, more preferably in the range of 0.4 to 1.2 mass %, based on the mass of the zeolitic material contained in the aqueous mixture prepared in step (i).
[0024] Preferably, the aqueous mixture prepared in step (i) comprises water, a zeolitic material comprising copper, a source of copper other than a zeolitic material comprising copper, and a non-zeolitic acidic material selected from the group consisting of alumina, silica, titania, zirconia, ceria, mixed oxides comprising one or more of Al, Si, Ti, Zr and Ce, and mixtures of two or more of these, and one or more acids as defined above.
[0025] Alternatively, it is preferred that the aqueous mixture prepared in step (i) comprises water, a zeolitic material comprising copper, a source of copper other than a zeolitic material comprising copper, and a non-zeolitic acidic material selected from the group consisting of alumina, silica, titania, zirconia, ceria, mixed oxides comprising one or more of Al, Si, Ti, Zr and Ce, and mixtures of two or more of these, a precursor of an acidic component as defined above, and more preferably one or more acids as defined above.
[0026] The aqueous mixture prepared in step (i) preferably further contains particles of a carbon-containing additive, and the carbon-containing additive contained in the aqueous mixture prepared in step (i) is more preferably one or more of graphite, synthetic graphite, carbon black, graphene, diamond, fullerene, carbon nanotube, and amorphous carbon, more preferably one or more of graphite, synthetic graphite, and graphene, more preferably one or more of graphite and synthetic graphite. The carbon-containing additive has a removal temperature in the range of 120 to 900 ° C, preferably in the range of 400 to 850 ° C, more preferably in the range of 500 to 800 ° C.
[0027] Furthermore, in the present invention, the term "removal temperature" is to be understood as the temperature at which at least 95% by weight of the carbon-containing additive is removed / burned off, preferably 97-100% by weight of the carbon-containing additive, more preferably 98-100% by weight of the carbon-containing additive. Thus, according to the present invention, this means that at most 5% by weight, preferably 0-3% by weight, more preferably 0-2% by weight of the carbon-containing additive used in the process of the present invention is present in the final catalyst.
[0028] The particles of the carbon-containing additive contained in the aqueous mixture prepared in step (i) preferably have a Dv50 in the range of 0.5 to 30 micrometers, more preferably in the range of 2 to 15 micrometers, more preferably in the range of 3 to 12 micrometers, more preferably in the range of 4 to 10 micrometers, more preferably in the range of 5 to 8 micrometers, where Dv50 is determined in accordance with Reference Example 3 herein.
[0029] Alternatively, the particles of the carbon-containing additive contained in the aqueous mixture prepared in step (i) preferably have a Dv50 in the range of 0.5 to 30 micrometers, more preferably in the range of 1 to 22 micrometers, more preferably in the range of 2 to 20 micrometers, more preferably in the range of 5 to 19 micrometers, where Dv50 is determined in accordance with Reference Example 3 herein.
[0030] More preferably, the particles of the carbon-containing additive contained in the aqueous mixture prepared in step (i) have a Dv90 in the range of 4 to 60 micrometers, more preferably in the range of 6 to 30 micrometers, more preferably in the range of 8 to 20 micrometers, more preferably in the range of 9 to 14 micrometers, more preferably in the range of 10 to 13 micrometers, where Dv90 is determined in accordance with Reference Example 3 herein.
[0031] Alternatively, it is preferred that the particles of the carbon-containing additive contained in the aqueous mixture prepared in step (i) have a Dv90 in the range of 4 to 80 micrometers, more preferably in the range of 4.5 to 60 micrometers, more preferably in the range of 5 to 45 micrometers, where Dv90 is determined in accordance with Reference Example 3 herein.
[0032] The particles of the carbon-containing additive contained in the aqueous mixture prepared in step (i) are preferably insoluble in water, more preferably insoluble in water at a temperature in the range of 10 to 40°C, more preferably in the range of 15 to 35°C, more preferably in the range of 17 to 25°C.
[0033] It is preferred that the aqueous mixture prepared in step (i) comprises particles of the carbon-containing additive in an amount in the range of 2 to 40% by weight, more preferably in the range of 4 to 30% by weight, more preferably in the range of 5 to 25% by weight, more preferably in the range of 5.5 to 15% by weight, based on the weight of the zeolitic material and non-zeolitic acidic material in the aqueous mixture prepared in step (i).
[0034] Alternatively, the carbon-containing additive contained in the aqueous mixture prepared in step (i) is preferably one or more of polyacrylate, microcrystalline cellulose, corn starch, styrene, poly(methyl methacrylate-co-ethylene glycol), polymethyl urea, and polymethyl methacrylate, more preferably one or more of polymethyl urea and polymethyl methacrylate, more preferably polymethyl urea, or more preferably polymethyl methacrylate. It is more preferable that the carbon-containing additive has a removal temperature in the range of 150 to 550°C, more preferably in the range of 180 to 500°C.
[0035] In the present invention, preferably 98 to 100% by mass, more preferably 99 to 100% by mass, more preferably 99.5 to 100% by mass, more preferably 99.9 to 100% by mass of the aqueous mixture prepared in step (i) consists of water, a copper-containing zeolitic material, a copper source other than a copper-containing zeolitic material, and a non-zeolitic acidic material selected from the group consisting of alumina, silica, titania, zirconia, ceria, mixed oxides containing one or more of Al, Si, Ti, Zr and Ce, and mixtures of two or more of these, and more preferably one or more acids as defined above.
[0036] Alternatively, it is preferred that 98 to 100% by mass, more preferably 99 to 100% by mass, more preferably 99.5 to 100% by mass, more preferably 99.9 to 100% by mass of the aqueous mixture prepared in step (i) consists of water, a copper-containing zeolitic material, a copper source other than a copper-containing zeolitic material, and a non-zeolitic acidic material selected from the group consisting of alumina, silica, titania, zirconia, ceria, mixed oxides containing one or more of Al, Si, Ti, Zr and Ce, and mixtures of two or more of these, a precursor of an acidic component as defined above, and more preferably one or more acids as defined above.
[0037] As a further alternative, it is preferred that from 98 to 100% by weight, more preferably from 99 to 100% by weight, more preferably from 99.5 to 100% by weight, more preferably from 99.9 to 100% by weight of the aqueous mixture prepared in step (i) consists of water, a copper-containing zeolitic material, a source of copper other than a copper-containing zeolitic material, and a non-zeolitic acidic material selected from the group consisting of alumina, silica, titania, zirconia, ceria, mixed oxides comprising one or more of Al, Si, Ti, Zr and Ce, and mixtures of two or more of these, precursors of an acidic component as defined above, particles of a carbon-containing additive, and more preferably one or more acids as defined above.
[0038] Regarding step (i), this is (i.1) preparing a first mixture comprising water and a source of copper other than a copper-containing zeolitic material; (i.2) milling the first mixture, more preferably until the particles of the first mixture have a Dv90 in the range of 0.5 to 20 micrometers (Dv90 is determined as described in Reference Example 3); (i.3) optionally adding a precursor of an acidic component as defined above to the first mixture obtained by step (i.1), more preferably step (i.2); (i.4) preparing a second mixture comprising water and a zeolitic material comprising copper; (i.5) mixing the second mixture obtained in step (i.4) with the first mixture obtained in step (i.1), more preferably in step (i.2) or step (i.3), to obtain a third mixture; (i.6) preparing a fourth mixture comprising water and a non-zeolitic acidic material selected from the group consisting of alumina, silica, titania, zirconia, ceria, mixed oxides comprising one or more of Al, Si, Ti, Zr and Ce, and mixtures of two or more of these, and more preferably an acid, more preferably an organic acid, more preferably tartaric acid; (i.7) mixing the fourth mixture obtained in step (i.6) with the third mixture obtained in step (i.5), preferably by adding an acid, more preferably an organic acid, more preferably acetic acid, and optionally by adding particles of a carbon-containing additive as defined above prior to the acid. Preferably, Step (i) optionally comprises steps (i.1) to (i.7).
[0039] Thus, the present invention preferably relates to a method for preparing a catalyst comprising a copper-containing zeolitic material, the method comprising the steps of: (i) preparing an aqueous mixture comprising water, a copper-containing zeolitic material, a source of copper other than a copper-containing zeolitic material, and a non-zeolitic acidic material selected from the group consisting of alumina, silica, titania, zirconia, ceria, mixed oxides comprising one or more of Al, Si, Ti, Zr and Ce, and mixtures of two or more of these, wherein the zeolitic material is selected from the group consisting of CHA, AEI, RTH, LEV, DDR, KFI, ERI, AFX, mixtures of two or more of these, and mixed types of two or more of these. and wherein the source of copper other than the copper-containing zeolitic material contained in the aqueous mixture prepared in step (i) is selected from the group consisting of copper acetate, copper oxide, mixtures thereof, more preferably copper oxide, more preferably CuO, wherein step (i) comprises (i.1) preparing a first mixture comprising water and a source of copper other than a copper-containing zeolitic material; (i.2) milling the first mixture, more preferably until the particles of the first mixture have a Dv90 in the range of 0.5 to 20 micrometers (Dv90 is determined as described in Reference Example 3); (i.3) optionally adding a precursor of an acidic component as defined above to the first mixture obtained by step (i.1), more preferably step (i.2); (i.4) preparing a second mixture comprising water and a zeolitic material comprising copper; (i.5) mixing the second mixture obtained in step (i.4) with the first mixture obtained in step (i.1), more preferably in step (i.2) or step (i.3), to obtain a third mixture; (i.6) preparing a fourth mixture comprising water and a non-zeolitic acidic material selected from the group consisting of alumina, silica, titania, zirconia, ceria, mixed oxides comprising one or more of Al, Si, Ti, Zr and Ce, and mixtures of two or more of these, and more preferably an acid, more preferably an organic acid, more preferably tartaric acid; (i.7) mixing the fourth mixture obtained in step (i.6) with the third mixture obtained in step (i.5) by adding, more preferably, an acid, more preferably an organic acid, more preferably acetic acid, and optionally, adding particles of a carbon-containing additive as defined above prior to the acid, (ii) disposing the mixture from step (i.7) on a surface of an interior wall of a substrate having an inlet end, an outlet end, a substrate axial length extending from said inlet end to said outlet end, and a plurality of passages extending through the substrate and defined by the interior wall of the substrate, and optionally drying the substrate with the mixture disposed thereon; (iii) calcining the substrate obtained in step (ii) Includes.
[0040] In the present invention, preferably 90-100% by weight, more preferably 93-99% by weight, more preferably 96-99% by weight of the copper source other than the copper-containing zeolitic material is present in undissolved form in the mixtures prepared in steps (i.1) and (i.2).
[0041] The grinding in step (i.2) is preferably carried out until the particles of the first mixture have a Dv90 in the range of 4 to 15 micrometers, more preferably in the range of 6 to 12 micrometers, where Dv90 is determined as described in Reference Example 3.
[0042] It is preferred that the first mixture obtained in (i.1), more preferably in step (i.2), has a solids content in the range of 4 to 30% by weight, more preferably in the range of 4 to 15% by weight, based on the weight of the first mixture.
[0043] It is preferred that the second mixture obtained in step (i.4) has a solid content in the range of 15 to 50 mass%, more preferably in the range of 20 to 45 mass%, more preferably in the range of 30 to 40 mass%, based on the mass of the second mixture. It is more preferred that the first mixture obtained in step (i.1), more preferably in step (i.2), has a solid content in the range of 4 to 30 mass%, preferably in the range of 4 to 15 mass%, based on the mass of the first mixture, and the second mixture obtained in step (i.4) has a solid content in the range of 15 to 50 mass%, more preferably in the range of 20 to 45 mass%, more preferably in the range of 30 to 40 mass%, based on the mass of the second mixture.
[0044] With regard to step (i.5), it is preferred that this further comprises milling the third mixture, more preferably until the particles of the third mixture have a Dv90 in the range of 0.5 to 20 micrometers, more preferably in the range of 2 to 15 micrometers, more preferably in the range of 2 to 10 micrometers, wherein Dv90 is determined as described in Reference Example 3.
[0045] It is preferred that the fourth mixture obtained in step (i.6) has a solids content in the range of 15 to 60% by mass, more preferably in the range of 25 to 45% by mass, more preferably in the range of 28 to 40% by mass, based on the mass of the fourth mixture.
[0046] It is preferred that the aqueous mixture obtained in step (i), more preferably in step (i.7), has a solids content in the range of 15 to 50% by weight, more preferably in the range of 20 to 45% by weight, more preferably in the range of 30 to 40% by weight, based on the weight of the aqueous mixture.
[0047] The placement of the mixture according to step (ii) is preferably carried out by spraying the mixture onto the substrate or by immersing the substrate into the mixture, more preferably by immersing the substrate into the mixture.
[0048] In step (ii), the mixture from step (i) is preferably disposed over x% of the axial length of the substrate from the inlet end to the outlet end, or from the outlet end to the inlet end, of the substrate, where x is in the range of 80 to 100, more preferably in the range of 90 to 100, more preferably in the range of 95 to 100, more preferably in the range of 98 to 100.
[0049] It is preferred that the substrate in step (ii) is a wall-flow filter substrate, more preferably one or more of a cordierite wall-flow filter substrate, a silicon carbide wall-flow filter substrate and an aluminium titanate wall-flow filter substrate, more preferably one or more of a silicon carbide wall-flow filter substrate and an aluminium titanate wall-flow filter substrate, more preferably a silicon carbide wall-flow filter substrate.
[0050] More preferably, the substrate in step (ii) is a wall-flow filter having a plurality of channels arranged in a honeycomb pattern, the channels per square inch (cpsi) being more preferably in the range of 200 to 800, more preferably in the range of 250 to 500, more preferably in the range of 300 to 400, and the average wall thickness being more preferably in the range of 6 to 15 mils, more preferably in the range of 8 to 13 mils.
[0051] Alternatively preferred, the substrate in step (ii) is a flow-through substrate, more preferably one or more of a cordierite flow-through substrate, a silicon carbide flow-through substrate and an aluminum titanate flow-through substrate, more preferably one or more of a silicon carbide flow-through substrate and a cordierite flow-through substrate, more preferably a cordierite flow-through substrate.
[0052] Thus, the present invention preferably relates to a method for preparing a catalyst comprising a copper-containing zeolitic material, the method comprising the steps of: (i) preparing an aqueous mixture comprising water, a copper-containing zeolitic material, a source of copper other than the copper-containing zeolitic material, and a non-zeolitic acidic material selected from the group consisting of alumina, silica, titania, zirconia, ceria, mixed oxides comprising one or more of Al, Si, Ti, Zr and Ce, and mixtures of two or more of these, wherein the zeolitic material has a framework type selected from the group consisting of CHA, AEI, RTH, LEV, DDR, KFI, ERI, AFX, mixtures of two or more of these, and mixtures of two or more of these, more preferably a framework type selected from the group consisting of CHA, AEI, RTH, AFX, mixtures of two or more of these, and mixtures of two or more of these, more preferably a framework type selected from the group consisting of CHA and AEI, more preferably having framework type CHA; and the source of copper other than the copper-containing zeolitic material contained in the aqueous mixture prepared in step (i) is selected from the group consisting of copper acetate, copper oxide, mixtures thereof, more preferably copper oxide, more preferably CuO, (ii) disposing the mixture obtained in step (i) on a surface of an inner wall of a substrate having an inlet end, an outlet end, a length in the substrate axial direction extending from the inlet end to the outlet end, and a plurality of passages penetrating the substrate and defined by the inner wall of the substrate, and optionally drying the substrate on which the mixture is disposed, wherein step (ii) disposes the mixture from step (i) over x% of the substrate axial length from the inlet end to the outlet end of the substrate, or from the outlet end to the inlet end of the substrate, where x is in the range of 80 to 100, more preferably in the range of 90 to 100, more preferably in the range of 95 to 100, more preferably in the range of 98 to 100; (iii) calcining the substrate obtained in step (ii) Including, More preferably, the substrate in step (ii) is a wall-flow filter substrate, more preferably one or more of a cordierite wall-flow filter substrate, a silicon carbide wall-flow filter substrate and an aluminium titanate wall-flow filter substrate, more preferably one or more of a silicon carbide wall-flow filter substrate and an aluminium titanate wall-flow filter substrate, more preferably a silicon carbide wall-flow filter substrate.
[0053] In the present invention, the drying in step (ii) is preferably carried out in a gas atmosphere having a temperature in the range of 60 to 300° C., more preferably in the range of 90 to 150° C., and the gas atmosphere more preferably contains oxygen.
[0054] The drying in step (ii) is preferably carried out in a gas atmosphere for a duration in the range of 10 minutes to 4 hours, more preferably in the range of 20 minutes to 3 hours, more preferably in the range of 50 minutes to 2.5 hours, and the gas atmosphere more preferably contains oxygen.
[0055] The arrangement according to step (ii) is (ii.1) disposing a first portion of the mixture obtained in step (i) on a surface of an inner wall of a substrate, the inner wall of the substrate having an inlet end, an outlet end, a length along an axial direction of the substrate extending from the inlet end to the outlet end, and a plurality of passages extending through the substrate and defined by the inner wall of the substrate; and drying the substrate on which the first portion of the mixture is disposed; (ii.2) disposing a second portion of the mixture obtained in step (i) on the substrate on which the first portion of the mixture obtained in step (ii.1) is disposed, and optionally drying the substrate on which the first and second portions of the mixture are disposed. It is preferred that the compound contains
[0056] It is preferred to further dilute the mixture obtained in step (i) before disposing a first portion of the mixture obtained in step (i) on the surface of the inner wall of the substrate according to step (ii.1).
[0057] It is preferred to further dilute the mixture obtained in step (i) before disposing a second portion of the mixture obtained in step (i) on the surface of the inner wall of the substrate according to step (ii.2).
[0058] By step (ii.1), it is preferred to dispose a first portion of the mixture from step (i) over x1% of the length in the axial direction of the substrate from the inlet end to the outlet end of the substrate or from the outlet end to the inlet end of the substrate, where x1 is in the range of 80 to 100, more preferably in the range of 90 to 100, more preferably in the range of 95 to 100, more preferably in the range of 98 to 100. By step (ii.2), it is more preferred to dispose a second portion of the mixture from step (i) over x2% of the length in the axial direction of the substrate from the inlet end to the outlet end of the substrate or from the outlet end to the inlet end of the substrate, where x2 is in the range of 80 to 100, more preferably in the range of 90 to 100, more preferably in the range of 95 to 100, more preferably in the range of 98 to 100, more preferably x2 is x1.
[0059] Thus, the present invention preferably relates to a method for preparing a catalyst comprising a copper-containing zeolitic material, the method comprising the steps of: (i) preparing an aqueous mixture comprising water, a copper-containing zeolitic material, a source of copper other than the copper-containing zeolitic material, and a non-zeolitic acidic material selected from the group consisting of alumina, silica, titania, zirconia, ceria, mixed oxides comprising one or more of Al, Si, Ti, Zr and Ce, and mixtures of two or more of these, wherein the zeolitic material has a framework type selected from the group consisting of CHA, AEI, RTH, LEV, DDR, KFI, ERI, AFX, mixtures of two or more of these, and mixtures of two or more of these, more preferably a framework type selected from the group consisting of CHA, AEI, RTH, AFX, mixtures of two or more of these, and mixtures of two or more of these, more preferably a framework type selected from the group consisting of CHA and AEI, more preferably having framework type CHA; and the source of copper other than the copper-containing zeolitic material contained in the aqueous mixture prepared in step (i) is selected from the group consisting of copper acetate, copper oxide, mixtures thereof, more preferably copper oxide, more preferably CuO, (ii) disposing the mixture from step (i) on a surface of an interior wall of a substrate having an inlet end, an outlet end, a substrate axial length extending from said inlet end to said outlet end, and a plurality of passages extending through the substrate and defined by the interior wall of the substrate, and optionally drying the substrate on which the mixture is disposed, wherein step (ii) comprises: (ii.1) disposing a first portion of the mixture obtained in step (i) on a surface of an inner wall of a substrate, the surface comprising an inlet end, an outlet end, a substrate axial length extending from the inlet end to the outlet end, and a plurality of passages penetrating the substrate and defined by the inner wall of the substrate, and drying the substrate on which the first portion of the mixture is disposed (wherein more preferably, the first portion of the mixture obtained in step (i) is disposed in step (ii.1) over x1% of the substrate axial length from the inlet end to the outlet end of the substrate or from the outlet end to the inlet end of the substrate, where x1 is in the range of 80 to 100, more preferably in the range of 90 to 100, more preferably in the range of 95 to 100, more preferably in the range of 98 to 100); (ii.2) disposing a second portion of the mixture obtained in step (i) on a substrate on which the first portion of the mixture obtained in step (ii.1) is disposed, and optionally drying the substrate on which the first and second portions of the mixture are disposed (wherein more preferably, in step (ii.2), the second portion of the mixture obtained in step (i) is disposed over x2% of the length in the axial direction of the substrate from the inlet end to the outlet end of the substrate or from the outlet end to the inlet end of the substrate, where x2 is in the range of 80 to 100, more preferably in the range of 90 to 100, more preferably in the range of 95 to 100, more preferably in the range of 98 to 100, and more preferably x2 is x1). (iii) calcining the substrate obtained in step (ii.2); Includes.
[0060] In the present invention, the drying in step (ii.1) is preferably carried out in a gas atmosphere having a temperature in the range of 60 to 300° C., more preferably in the range of 90 to 150° C., the gas atmosphere more preferably containing oxygen.
[0061] The drying according to step (ii.1) is preferably carried out in a gas atmosphere for a duration ranging from 10 minutes to 4 hours, more preferably from 20 minutes to 3 hours, more preferably from 50 minutes to 2.5 hours, the gas atmosphere preferably comprising oxygen.
[0062] For drying according to step (ii.2), it is preferred that this is carried out in a gas atmosphere having a temperature in the range of 60-300° C., more preferably in the range of 90-150° C., the gas atmosphere more preferably containing oxygen.
[0063] The drying according to step (ii.2) is preferably carried out in a gas atmosphere for a duration ranging from 10 minutes to 4 hours, more preferably from 20 minutes to 3 hours, more preferably from 50 minutes to 2.5 hours, the gas atmosphere preferably comprising oxygen.
[0064] For the calcination in step (iii), it is preferred to carry out this in a gas atmosphere having a temperature in the range of 300-900°C, more preferably in the range of 400-650°C, more preferably in the range of 400-500°C, or more preferably in the range of 550-600°C, the gas atmosphere more preferably containing oxygen, or it is preferred to carry out this in a gas atmosphere having a temperature in the range of 700-900°C, the gas atmosphere more preferably containing oxygen.
[0065] For the calcination according to step (iii), it is preferred that this is carried out for a duration ranging from 0.1 to 4 hours, more preferably ranging from 0.5 to 2.5 hours, in a gas atmosphere, which more preferably contains oxygen.
[0066] It is preferred that the mass ratio of copper (calculated as CuO) contained in the zeolite material contained in the substrate obtained in step (iii) to copper (calculated as CuO) contained in the zeolite material contained in the mixture from step (i) is in the range of 1.5:1 to 10:1, preferably in the range of 2:1 to 5:1, and more preferably in the range of 2:1 to 4:1.
[0067] Preferably, the process according to the invention comprises steps (i), (ii) and (iii).
[0068] In the process for preparing a catalyst comprising a copper-containing zeolitic material according to the present invention, it is preferred that the aqueous mixture prepared according to step (i) is an aqueous mixture according to the present invention and as disclosed herein below in paragraph II.
[0069] The present invention further relates to a catalyst comprising a zeolitic material containing copper, said catalyst being obtained or obtainable by the process for preparing a catalyst according to the present invention.
[0070] The amount of copper contained in the catalyst, calculated as CuO, is preferably in the range of 2 to 10 mass %, more preferably in the range of 2.5 to 5.5 mass %, more preferably in the range of 2.5 to 5 mass %, based on the mass of the zeolite material.
[0071] Preferably, 75 to 100 mass %, more preferably 78 to 100 mass %, and more preferably 80 to 100 mass % of the copper contained in the catalyst is contained in the zeolite material.
[0072] Preferably, the amount of copper in the zeolite contained in the catalyst is greater than the amount of copper contained in the zeolitic material contained in the mixture from step (i).
[0073] Catalyst: 0.8 to 2.6 g / in 3 More preferably, the range is 1.2 to 2.2 g / in 3 More preferably, the range is 1.5 to 2.2 g / in 3 It is preferred to include the zeolite material at a loading in the range of 100-200 μm.
[0074] Catalyst is 0.02 to 0.52 g / in 3 More preferably, the range is 0.1 to 0.42 g / in 3 More preferably, the range is 0.1 to 0.21 g / in 3 It is preferred to include the non-zeolitic acidic material at a loading in the range of 0.1 to 1.0.
[0075] It is preferred that the catalyst comprises non-zeolitic acidic material in an amount in the range 2 to 20% by weight, more preferably in the range 5 to 15% by weight, more preferably in the range 7 to 13% by weight, based on the weight of the zeolitic material.
[0076] It is preferred that the catalyst further contains an acidic component, which is selected from the group consisting of alumina, silica, zirconia, titania, mixed oxides containing two or more of Si, Al, Zr and Ti, and mixtures of two or more of these, more preferably selected from the group consisting of alumina, zirconia, mixed oxides of Al and Zr, and mixtures thereof, and the acidic component is more preferably zirconia. 3 More preferably, the range is 0.4 to 0.2 g / in 3 More preferably, the range is 0.06 to 0.14 g / in 3 It is more preferable that the acidic component is contained in an amount within the range of 1.
[0077] Preferably, the catalyst comprises a coating disposed on the surface of the inner wall of the substrate, the coating comprising a copper-containing zeolitic material, a non-zeolitic acidic material, and optionally an acidic component as defined above. More preferably, the coating is disposed on the surface of the inner wall of the substrate over 80-100%, more preferably over 90-100%, more preferably over 95-100%, more preferably over 98-100% of the axial length of the substrate.
[0078] The catalyst of the present invention preferably exhibits a NOx activity, determined as defined in Example 2, which is higher than the NOx activity of a catalyst prepared in the same manner except for step (i) being replaced by step (I1), where step (I1) comprises the preparation of an aqueous mixture comprising water, a zeolitic material in H form, a source of copper, and a non-zeolitic acidic material selected from the group consisting of alumina, silica, titania, zirconia, ceria, mixed oxides comprising one or more of Al, Si, Ti, Zr and Ce, and mixtures of two or more of these; The amount of copper contained in the aqueous mixture prepared in step (I1), calculated as CuO, is equal to the amount of copper contained in the aqueous mixture prepared in step (i), which amount of copper contained in the aqueous mixture prepared in step (i) includes the amount of copper contained in the copper-containing zeolitic material used in step (i) and the amount of copper from the copper source used in step (i).
[0079] It is preferred that the catalyst has a NOx conversion activity, determined as defined in Example 2, which is higher than the NOx conversion activity of a catalyst comprising a zeolitic material containing copper other than a catalyst obtained or obtainable by the process of the present invention under the same conditions and with the same loading.
[0080] The copper-containing zeolitic material contained in the catalyst according to the invention is preferably a zeolitic material according to the invention and as disclosed herein below in paragraph III.
[0081] Preferably, 98 to 100% by mass, more preferably 99 to 100% by mass, and more preferably 99.5 to 100% by mass of the catalyst is composed of a zeolite material containing copper, and a non-zeolite acidic material selected from the group consisting of alumina, silica, titania, zirconia, ceria, a mixed oxide containing one or more of Al, Si, Ti, Zr, and Ce, and a mixture of two or more of these, and a substrate. Alternatively, 98 to 100% by mass, more preferably 99 to 100% by mass, and more preferably 99.5 to 100% by mass of the catalyst is composed of a zeolite material containing copper, and a non-zeolite acidic material selected from the group consisting of alumina, silica, titania, zirconia, ceria, a mixed oxide containing one or more of Al, Si, Ti, Zr, and Ce, and a mixture of two or more of these, and a substrate, and an acidic component as defined above.
[0082] The catalyst of the present invention is preferably a selective catalytic reduction catalyst.
[0083] The invention further relates to the use of the catalyst according to the invention for the selective catalytic reduction of nitrogen oxides.
[0084] The present invention further relates to a method for selective catalytic reduction of nitrogen oxides, wherein the nitrogen oxides are contained in an exhaust gas stream, said method comprising: (1) providing an exhaust gas stream, preferably from a compression ignition engine; (2) passing the exhaust gas stream provided in (1) through a selective catalytic reduction catalyst according to the present invention; Includes.
[0085] The present invention further relates to an exhaust gas treatment system for treating an exhaust gas stream exiting a compression ignition engine, said exhaust gas treatment system having an upstream end for introducing said exhaust gas stream into said exhaust gas treatment system, said exhaust gas treatment system comprising a catalyst according to the present invention and one or more of a diesel oxidation catalyst, a selective catalytic reduction catalyst, an ammonia oxidation catalyst, a NOx trap, and a particulate filter.
[0086] The exhaust gas treatment system preferably comprises a diesel oxidation catalyst arranged downstream of the engine and upstream of the catalyst according to the invention, optionally said diesel oxidation catalyst containing a NOx storage function.
[0087] The exhaust gas treatment system preferably further comprises one or more of a selective catalytic reduction catalyst and an ammonia oxidation catalyst disposed downstream of the catalyst according to the present invention.
[0088] Preferably, the exhaust gas treatment system further comprises a selective catalytic reduction catalyst positioned downstream of the diesel oxidation catalyst and upstream of the catalyst according to the present invention.
[0089] II. Aqueous Mixtures and Methods for Preparing the Same The present invention further relates to an aqueous mixture comprising water, a zeolitic material comprising copper, a source of copper other than a zeolitic material comprising copper, and a non-zeolitic acidic material selected from the group consisting of alumina, silica, titania, zirconia, ceria, mixed oxides comprising one or more of Al, Si, Ti, Zr and Ce, and mixtures of two or more thereof.
[0090] Zeolite materials containing copper are ABW, ACO, AEI, AEL, AEN, AET, AFG, AFI, AFN, AFO, AFR, AFS, AFT, AFV, AFX, AFY, AHT, ANA, APC, APD, AST, ASV, ATN, ATO, ATS, ATT, ATV, AVL, AWO, AWW, BCT, BEA, BE. C, BIK, BOF, BOG, BOZ, BPH, BRE, BSV, CAN, CAS, CDO, CFI, CGF, CGS, CHA, -CHI, -CLO, CON, CSV, CZP, DAC, DDR, DFO, DFT, DOH, DON, EAB, EDI, EEI, EMT, EON, EPI, ERI, ESV, ETR, EUO, * -EWT, EZT, FAR, FAU, FER, FRA, GIS, GIU, GME, GON, GOO, HEU, IFO, IFR, -IFU, IFW, IFY, IHW, IMF, IRN, IRR, -IRY, ISV, ITE, ITG, ITH, * -ITN, ITR, ITT, -ITV, ITW, IWR, IWS, IWV, IWW, JBW, JNT, JOZ, JRY, JSN, JSR, JST, JSW, KFI, LAU, LEV , LIO, -LIT, LOS, LOV, LTA, LTF, LTJ, LTL, LTN, MAR, MAZ, MEI, MEL, MEP, MER, MFI, MFS, MON, MOR, MOZ, *MRE, MSE, MSO, MTF, MTN, MTT, MTW, MVY, MWF, MWW, NAB, NAT, NES, NON, NPO, NPT, NSI, OBW, OFF, OKO, OSI, OSO, OWE, -PAR, PAU, PCR, PHI, PON, PO S, PSI, PUN, RHO, -RON, RRO, RSN, RTE, RTH, RUT, RWR, RWY, SAF, SAO, SAS, SAT, SAV, SBE, SBN, SBS, SBT, SEW, SFE, SFF, SFG, SFH, SFN, SFO, SFS, * SFV, SFW, SGT, SIV, SOD, SOF, SOS, SSF, * -SSO, SSY, STF, STI, * It is preferred that the zeolite material containing copper has a framework type selected from the group consisting of STO, STT, STW, -SVR, SVV, SZR, TER, THO, TOL, TON, TSC, TUN, UEI, UFI, UOS, UOV, UOZ, USI, UTL, UWY, VET, VFI, VNI, VSV, WEI, -WEN, YUG, ZON, a mixture of two or more of these, and a mixed type of two or more of these. It is more preferred that the zeolite material containing copper has a framework type selected from the group consisting of CHA, AEI, RTH, LEV, DDR, KFI, ERI, AFX, a mixture of two or more of these, and a mixed type of two or more of these, more preferably a framework type selected from the group consisting of CHA, AEI, RTH, AFX, a mixture of two or more of these, and a mixed type of two or more of these, more preferably a framework type selected from the group consisting of CHA and AEI. It is more preferred that the zeolite material containing copper has a framework type CHA.
[0091] Preferably, 95-100% by mass, more preferably 98-100% by mass, more preferably 99-100% by mass of the framework structure of the zeolite material is composed of Si, Al, and O, and the molar ratio of Si to Al in the framework structure, calculated as molar SiO2:Al2O3, is more preferably in the range of 2:1-50:1, more preferably in the range of 5:1-45:1, more preferably in the range of 10:1-35:1, more preferably in the range of 16:1-28:1. It is more preferred that the copper-containing zeolite material has framework type CHA, and the molar ratio of Si to Al, calculated as molar SiO2:Al2O3, is in the range of 2:1-50:1, more preferably in the range of 5:1-45:1, more preferably in the range of 10:1-35:1, more preferably in the range of 16:1-28:1, more preferably in the range of 16:1-19:1, or more preferably in the range of 23:1-27:1.
[0092] It is preferred that the zeolitic material, more preferably a zeolitic material having framework CHA, has an average crystallite size, as determined by scanning electron microscopy, of at least 0.1 micrometer, more preferably in the range of 0.1 to 3.0 micrometers, more preferably in the range of 0.3 to 1.5 micrometers, more preferably in the range of 0.4 to 1.0 micrometers.
[0093] The amount of copper contained in the zeolite material, calculated as CuO, is preferably in the range of 0.05 to 3.5 mass%, more preferably in the range of 0.1 to 3 mass%, more preferably in the range of 0.2 to 2 mass%, more preferably in the range of 0.5 to 1.75 mass%, more preferably in the range of 1 to 1.75 mass%, or more preferably in the range of 1.9 to 2.5 mass%, based on the mass of the zeolite material.
[0094] It is preferred that the source of copper other than the copper-containing zeolitic material is selected from the group consisting of copper acetate, copper nitrate, copper sulfate, copper formate, copper oxide, and mixtures of two or more thereof, more preferably selected from the group consisting of copper acetate, copper oxide, and mixtures of two or more thereof, more preferably copper oxide, more preferably CuO.
[0095] It is preferred that the aqueous mixture contains a source of copper other than the copper-containing zeolitic material in an amount, calculated as CuO, in the range of 0.1 to 14% by mass, more preferably in the range of 0.5 to 12% by mass, more preferably in the range of 1 to 10% by mass, more preferably in the range of 1.5 to 5% by mass, more preferably in the range of 1.5 to 4.5% by mass, based on the mass of the zeolitic material. It is even more preferred that the aqueous mixture contains a source of copper other than the copper-containing zeolitic material in an amount, calculated as CuO, in the range of 1.5 to 4% by mass, based on the mass of the zeolitic material. It is more preferred that the source of copper other than the copper-containing zeolitic material is selected from the group consisting of copper acetate, copper oxide, and a mixture of two or more thereof, more preferably copper oxide, more preferably CuO, and the aqueous mixture contains said source of copper other than the copper-containing zeolitic material in an amount, calculated as CuO, in the range of 0.5 to 12% by mass, more preferably in the range of 1 to 10% by mass, more preferably in the range of 1.5 to 5% by mass, more preferably in the range of 1.5 to 4% by mass, based on the mass of the zeolitic material.
[0096] The non-zeolitic acidic material is preferably selected from the group consisting of alumina, silica, titania, mixed oxides containing one or more of Al, Si, and Ti, and mixtures of two or more of these, preferably selected from the group consisting of alumina, silica, mixed oxides containing one or more of Al and Si, and mixtures of two or more of these, more preferably a mixture of alumina and silica. It is more preferable that 80 to 99 mass %, more preferably 85 to 98 mass %, more preferably 90 to 98 mass % of the mixture of alumina and silica is made of alumina, and more preferably 1 to 20 mass %, more preferably 2 to 15 mass %, more preferably 2 to 10 mass % of the mixture of alumina and silica is made of silica.
[0097] The aqueous mixture preferably comprises the non-zeolitic acidic material in an amount in the range of 2 to 20% by weight, preferably in the range of 5 to 15% by weight, more preferably in the range of 7 to 13% by weight, based on the weight of the zeolitic material.
[0098] The aqueous mixture preferably comprises 10 to 90% by mass, more preferably 40 to 85% by mass, and more preferably 55 to 80% by mass of water.
[0099] The aqueous mixture preferably further comprises a precursor of the acidic component, the precursor being more preferably one or more of an aluminum salt, a silicon salt, a zirconium salt, and a titanium salt, more preferably one or more of a zirconium salt and an aluminum salt, more preferably a zirconium salt, more preferably zirconium acetate. More preferably, in the aqueous mixture, the amount of precursor calculated as oxide, more preferably alumina, silica, zirconia or titania, more preferably the amount of zirconium salt calculated as ZrO2, is in the range of 1-10% by weight, more preferably in the range of 2-8% by weight, more preferably in the range of 3-7% by weight, based on the weight of the zeolitic material.
[0100] The aqueous mixture may further include particles of a carbon-containing additive. The carbon-containing additive contained in the mixture is preferably one or more of graphite, synthetic graphite, carbon black, graphene, diamond, fullerene, carbon nanotube, and amorphous carbon, more preferably one or more of graphite, synthetic graphite, graphene, fullerene, carbon nanotube, and amorphous carbon, more preferably one or more of graphite, synthetic graphite, and graphene, and more preferably one or more of graphite and synthetic graphite.
[0101] The carbon-containing additive has a removal temperature in the range of 120-900° C., preferably in the range of 400-850° C., more preferably in the range of 500-800° C. The definition of the term “removal temperature” is understood as given in paragraph I.
[0102] The particles of the carbon-containing additive contained in the mixture preferably have a Dv50 in the range of 0.5 to 30 micrometers, more preferably in the range of 2 to 15 micrometers, more preferably in the range of 3 to 12 micrometers, more preferably in the range of 4 to 10 micrometers, more preferably in the range of 5 to 8 micrometers, where Dv50 is determined in accordance with Reference Example 3 herein.
[0103] Alternatively, the particles of the carbon-containing additive contained in the mixture preferably have a Dv50 in the range of 0.5 to 30 micrometers, more preferably in the range of 1 to 22 micrometers, more preferably in the range of 2 to 20 micrometers, more preferably in the range of 5 to 19 micrometers, where Dv50 is determined in accordance with Reference Example 3 herein.
[0104] The particles of the carbon-containing additive contained in the mixture preferably have a Dv90 in the range of 4 to 60 micrometers, more preferably in the range of 6 to 30 micrometers, more preferably in the range of 8 to 20 micrometers, more preferably in the range of 9 to 14 micrometers, more preferably in the range of 10 to 13 micrometers, where Dv90 is determined in accordance with Reference Example 3 herein.
[0105] Alternatively, the particles of the carbon-containing additive contained in the mixture have a Dv90 in the range of 4 to 80 micrometers, more preferably in the range of 4.5 to 60 micrometers, more preferably in the range of 5 to 45 micrometers, where Dv90 is determined in accordance with Reference Example 3 herein.
[0106] The mixture may comprise particles of the carbon-containing additive in an amount in the range of 2 to 40% by weight, more preferably in the range of 4 to 30% by weight, more preferably in the range of 5 to 25% by weight, more preferably in the range of 5.5 to 15% by weight, based on the weight of the zeolitic material and non-zeolitic acidic material in the mixture.
[0107] Alternatively, the carbon-containing additive contained in the mixture is preferably one or more of polyacrylate, microcrystalline cellulose, corn starch, styrene, poly(methyl methacrylate-co-ethylene glycol), polymethyl urea, and polymethyl methacrylate, more preferably one or more of polymethyl urea and polymethyl methacrylate, more preferably polymethyl urea, or more preferably polymethyl methacrylate. It is more preferable that the carbon-containing additive has a removal temperature in the range of 150 to 550°C, more preferably in the range of 180 to 500°C.
[0108] The aqueous mixture may further comprise one or more additional non-zeolitic acidic materials selected from the group consisting of alumina, silica, titania, zirconia, ceria, mixed oxides comprising one or more of Al, Si, Ti, Zr, and Ce, and mixtures of two or more thereof.
[0109] The aqueous mixture preferably further comprises one or more acids, more preferably two acids, more preferably two organic acids, more preferably tartaric acid and acetic acid, more preferably in an amount in the range of 0.1 to 2% by weight, more preferably in the range of 0.2 to 1.5% by weight, more preferably in the range of 0.4 to 1.2% by weight, based on the weight of the zeolitic material.
[0110] The aqueous mixture preferably has a solids content in the range of 15 to 50% by mass, more preferably in the range of 20 to 45% by mass, more preferably in the range of 30 to 40% by mass, based on the weight of the aqueous mixture.
[0111] The aqueous mixture preferably comprises water, a zeolitic material comprising copper, a source of copper other than the zeolitic material comprising copper, and a non-zeolitic acidic material selected from the group consisting of alumina, silica, titania, zirconia, ceria, mixed oxides comprising one or more of Al, Si, Ti, Zr and Ce, and mixtures of two or more of these, and one or more acids as defined above. Alternatively, the aqueous mixture preferably comprises water, a zeolitic material comprising copper, a source of copper other than the zeolitic material comprising copper, and a non-zeolitic acidic material selected from the group consisting of alumina, silica, titania, zirconia, ceria, mixed oxides comprising one or more of Al, Si, Ti, Zr and Ce, and mixtures of two or more of these, a precursor of an acidic component as defined above, and more preferably one or more acids as defined above. As a further alternative, the aqueous mixture preferably comprises water, a zeolitic material comprising copper, a source of copper other than a zeolitic material comprising copper, and a non-zeolitic acidic material selected from the group consisting of alumina, silica, titania, zirconia, ceria, mixed oxides comprising one or more of Al, Si, Ti, Zr and Ce, and mixtures of two or more of these, a precursor of an acidic component as defined above, particles of a carbon-containing additive as defined above, and more preferably one or more acids as defined above.
[0112] In the present invention, it is preferred that 98 to 100% by mass, more preferably 99 to 100% by mass, more preferably 99.5 to 100% by mass, and more preferably 99.9 to 100% by mass of the mixture consists of water, a copper-containing zeolitic material, a copper source other than a copper-containing zeolitic material, and a non-zeolitic acidic material selected from the group consisting of alumina, silica, titania, zirconia, ceria, mixed oxides containing one or more of Al, Si, Ti, Zr and Ce, and mixtures of two or more of these, and more preferably one or more acids as defined above. It is alternatively preferred that from 98 to 100% by weight, more preferably from 99 to 100% by weight, more preferably from 99.5 to 100% by weight, more preferably from 99.9 to 100% by weight of the mixture consists of water, a copper-containing zeolitic material, a source of copper other than a copper-containing zeolitic material, and a non-zeolitic acidic material selected from the group consisting of alumina, silica, titania, zirconia, ceria, mixed oxides containing one or more of Al, Si, Ti, Zr and Ce, and mixtures of two or more of these, precursors of an acidic component as defined above, and more preferably one or more acids as defined above. As a further alternative, it is preferred that from 98 to 100% by weight, more preferably from 99 to 100% by weight, more preferably from 99.5 to 100% by weight, more preferably from 99.9 to 100% by weight of the mixture consists of water, a zeolitic material comprising copper, a source of copper other than a zeolitic material comprising copper, and a non-zeolitic acidic material selected from the group consisting of alumina, silica, titania, zirconia, ceria, mixed oxides comprising one or more of Al, Si, Ti, Zr and Ce, and mixtures of two or more of these, precursors of an acidic component as defined above, particles of a carbon-containing additive as defined above, and more preferably one or more acids as defined above.
[0113] The aqueous mixture according to the invention is preferably the aqueous mixture prepared in step (i) in the process for preparing the catalyst according to the invention and disclosed in paragraph I. above.
[0114] The present invention further relates to a method for preparing a mixture according to the invention, which method comprises the steps of: (i.1) preparing a first mixture comprising water and a source of copper other than a copper-containing zeolitic material; (i.2) optionally a precursor of the acidic component as defined above in the first mixture obtained by step (i.1), (i.3) preparing a second mixture comprising water and a zeolitic material comprising copper; (i.4) mixing the second mixture obtained in step (i.3) with the first mixture obtained in step (i.1) or in step (i.2) to obtain a third mixture; (i.5) preparing a fourth mixture comprising water and a non-zeolitic acidic material selected from the group consisting of alumina, silica, titania, zirconia, ceria, mixed oxides comprising one or more of Al, Si, Ti, Zr and Ce, and mixtures of two or more of these, and more preferably an acid, more preferably an organic acid, more preferably tartaric acid; (i.6) mixing the fourth mixture obtained in step (i.5) with the third mixture obtained in step (i.4), preferably by adding an acid, more preferably an organic acid, more preferably acetic acid, and optionally by adding particles of a carbon-containing additive as defined above prior to the acid. Includes.
[0115] Preferably, 90-100% by mass, more preferably 95-100% by mass, more preferably 96-99% by mass of the source of copper other than the copper-containing zeolitic material is present in undissolved state in the mixture prepared in step (i.1).
[0116] With regard to step (i.1), it is preferred that this further comprises milling the first mixture, more preferably until the particles of the first mixture have a Dv90 in the range of 0.5 to 20 micrometers, more preferably in the range of 4 to 15 micrometers, more preferably in the range of 6 to 12 micrometers, where Dv90 is determined as described in Reference Example 3.
[0117] It is preferred that the first mixture obtained in step (i.1) has a solids content in the range of 4 to 30% by mass, more preferably in the range of 4 to 15% by mass, based on the mass of the first mixture.
[0118] It is preferred that the second mixture obtained in step (i.3) has a solids content in the range of 15 to 50% by mass, more preferably in the range of 20 to 45% by mass, more preferably in the range of 30 to 40% by mass, based on the mass of the second mixture.
[0119] With regard to step (i.4), it is preferred that this further comprises milling the third mixture, more preferably until the particles of the third mixture have a Dv90 in the range of 0.5 to 20 micrometers, more preferably in the range of 2 to 15 micrometers, more preferably in the range of 2 to 10 micrometers, wherein Dv90 is determined as described in Reference Example 3.
[0120] It is preferred that the fourth mixture obtained in step (i.5) has a solids content in the range of 15 to 50% by mass, more preferably in the range of 20 to 45% by mass, more preferably in the range of 28 to 40% by mass, based on the mass of the fourth mixture.
[0121] It is preferred that the aqueous mixture obtained in step (i), more preferably in step (i.6), has a solids content in the range of 15 to 50% by weight, more preferably in the range of 20 to 45% by weight, more preferably in the range of 30 to 40% by weight, based on the weight of the aqueous mixture.
[0122] The process according to the invention preferably comprises steps (i.1), (i.2), (i.3), (i.4), (i.5) and (i.6).
[0123] The present invention further relates to the aqueous mixture disclosed above, which is obtained or obtainable by the process according to the invention.
[0124] The present invention further relates to the use of the aqueous mixture according to the invention for the preparation of a catalyst, preferably a selective catalytic reduction catalyst.
[0125] Surprisingly, it has been found that the use of the aqueous mixture according to the present invention, particularly in a process for preparing a catalyst, can provide a catalyst comprising a copper-containing zeolitic material that exhibits high catalytic activity, e.g., NOx conversion, at both low and high temperatures.
[0126] The present invention further provides a method for preparing a catalyst, preferably a selective catalytic reduction catalyst, comprising the steps of: Use of the aqueous mixture according to the invention The present invention relates to a method comprising the steps of:
[0127] III. Zeolitic Materials Having Framework-Type CHA and Containing Copper The present invention further relates to a zeolitic material having framework type CHA and containing copper, the framework structure of the zeolitic material containing Si, Al, and O and determined as described in Example 12, as follows: Maximum value: 930~975cm -1 in the range of 935 to 970 cm -1 More preferably, in the range of 945 to 965 cm -1 a first absorption peak (P1) having a range of Maximum value: 880~920cm -1 in the range of 885 to 915 cm -1 More preferably, the range is 890 to 910 cm -1 a second absorption peak (P2) having a range of The IR spectrum includes The ratio P1:P2 of the peak area of the first absorption peak to the peak area of the second absorption peak is in the range of 0.2:1 to 1.55:1, preferably in the range of 0.5:1 to 1.53:1, more preferably in the range of 1.05:1 to 1.53:1, more preferably in the range of 1.07:1 to 1.45:1, more preferably in the range of 1.10:1 to 1.40:1, more preferably in the range of 1.12:1 to 1.35:1, and more preferably in the range of 1.15:1 to 1.32:1.
[0128] Preferably, 95 to 100 mass%, more preferably 98 to 100 mass%, more preferably 99 to 100 mass% of the framework structure of the zeolite material consists of Si, Al and O, and the molar ratio of Si to Al in the framework structure, calculated as molar SiO2:Al2O3, is more preferably in the range of 2:1 to 50:1, more preferably in the range of 5:1 to 45:1, more preferably in the range of 10:1 to 35:1, more preferably in the range of 16:1 to 28:1, more preferably in the range of 16:1 to 19:1, or more preferably in the range of 23:1 to 27:1.
[0129] It is preferred that the zeolitic material has an average crystallite size, as determined by scanning electron microscopy, of at least 0.1 micrometer, more preferably in the range of 0.1 to 3.0 micrometers, more preferably in the range of 0.3 to 1.5 micrometers, more preferably in the range of 0.4 to 1.0 micrometers.
[0130] The amount of copper contained in the zeolite material, calculated as CuO, is preferably in the range of 0.1 to 14 mass%, more preferably in the range of 0.5 to 12 mass%, more preferably in the range of 1 to 10 mass%, more preferably in the range of 1.5 to 5 mass%, and more preferably in the range of 1.5 to 4.5 mass%, based on the mass of the zeolite material.
[0131] The peak area of the first absorption peak is 890 to 965 cm -1 The ratio of the area of all absorption peaks having a maximum value in this wavelength range to the total peak area is preferably in the range of 0.05:1 to 0.50:1, more preferably in the range of 0.08:1 to 0.5:1, more preferably in the range of 0.1:1 to 0.5:1, more preferably in the range of 0.15:1 to 0.49:1, more preferably in the range of 0.25:1 to 0.48:1, more preferably in the range of 0.30:1 to 0.45:1, and more preferably in the range of 0.40:1 to 0.45:1.
[0132] The zeolite material is preferably 400 to 800 m 2 / g, more preferably 500 to 700m 2 / g, the BET specific surface area being determined as described in Reference Example 1.
[0133] A zeolitic material having framework-type CHA and containing copper is preferably included in the catalyst according to the invention as described in paragraph I. above.
[0134] The present invention further relates to a method for preparing a zeolitic material according to the invention, comprising the steps of: (i) preparing an aqueous mixture comprising water, a zeolitic material having a framework CHA and containing copper, and a source of copper other than the copper-containing zeolitic material; (ii) optionally drying the mixture obtained in step (i); (iii) calcining the mixture obtained in step (i) or step (ii). Includes.
[0135] Preferably, 95 to 100 mass%, more preferably 98 to 100 mass%, more preferably 99 to 100 mass% of the framework structure of the zeolite material consists of Si, Al and O, and the molar ratio of Si to Al in the framework structure, calculated as molar SiO2:Al2O3, is more preferably in the range of 2:1 to 50:1, more preferably in the range of 5:1 to 45:1, more preferably in the range of 10:1 to 35:1, more preferably in the range of 16:1 to 28:1, more preferably in the range of 16:1 to 19:1, or more preferably in the range of 23:1 to 27:1.
[0136] It is preferred that the zeolitic material contained in the aqueous mixture prepared in step (i) has an average crystallite size, as determined by scanning electron microscopy, of at least 0.1 micrometer, more preferably in the range of 0.1 to 3.0 micrometer, more preferably in the range of 0.3 to 1.5 micrometer, more preferably in the range of 0.4 to 1.0 micrometer.
[0137] It is preferred that the amount of copper contained in the zeolitic material contained in the aqueous mixture prepared in step (i), calculated as CuO, is in the range of 0.05 to 3.5 mass%, more preferably in the range of 0.1 to 3 mass%, more preferably in the range of 0.2 to 2 mass%, more preferably in the range of 0.5 to 1.75 mass%, more preferably in the range of 1 to 1.75 mass%, or more preferably in the range of 1.9 to 2.5 mass%, based on the mass of the zeolitic material contained in the aqueous mixture prepared in step (i).
[0138] It is preferred that the source of copper other than the copper-containing zeolitic material is selected from the group consisting of copper acetate, copper nitrate, copper sulfate, copper formate, copper oxide, and mixtures of two or more thereof, more preferably selected from the group consisting of copper acetate, copper oxide, and mixtures of two or more thereof, more preferably copper oxide, more preferably CuO.
[0139] The aqueous mixture prepared in step (i) preferably contains a source of copper other than the copper-containing zeolitic material in an amount, calculated as CuO, in the range of 0.1 to 14 mass %, more preferably in the range of 0.5 to 12 mass %, more preferably in the range of 1 to 10 mass %, more preferably in the range of 1.5 to 5 mass %, based on the mass of the zeolitic material contained in the aqueous mixture prepared in step (i). It is more preferred that the aqueous mixture prepared in step (i) contains a source of copper other than the copper-containing zeolitic material in an amount, calculated as CuO, in the range of 1.5 to 4.5 mass %, more preferably in the range of 1.5 to 4 mass %, based on the mass of the zeolitic material contained in the aqueous mixture prepared in step (i).
[0140] In the aqueous mixture prepared in step (i), it is preferred that 10 to 90% by mass of the aqueous mixture is made up of water, more preferably 40 to 85% by mass, and more preferably 55 to 80% by mass.
[0141] It is preferred that the aqueous mixture prepared in step (i) further comprises a non-zeolitic acidic material selected from the group consisting of alumina, silica, titania, zirconia, ceria, mixed oxides containing one or more of Al, Si, Ti, Zr and Ce, and mixtures of two or more of these. It is more preferred that the non-zeolitic acidic material contained in the aqueous mixture prepared in step (i) is selected from the group consisting of alumina, silica, titania, mixed oxides containing one or more of Al, Si and Ti, and mixtures of two or more of these, preferably alumina, silica, mixed oxides containing one or more of Al and Si, and mixtures of two or more of these, more preferably a mixture of alumina and silica. The non-zeolitic material is preferably as defined in paragraphs I. and II. above.
[0142] It is preferred that the aqueous mixture prepared in step (i) further comprises one or more acids as defined above in paragraphs I and II. Additionally, optionally, the aqueous mixture prepared in step (i) further comprises particles of a carbon-containing additive as defined above in paragraphs I and II.
[0143] It is preferred that the aqueous mixture prepared in step (i) further comprises a precursor of the acidic component, and the precursor is more preferably one or more of an aluminum salt, a silicon salt, a zirconium salt, and a titanium salt, more preferably one or more of a zirconium salt and an aluminum salt, more preferably a zirconium salt, more preferably zirconium acetate. In the aqueous mixture prepared in step (i), the amount of the precursor calculated as an oxide, more preferably alumina, silica, zirconia, or titania, more preferably the amount of the zirconium salt calculated as ZrO2, is more preferably in the range of 1 to 10% by mass, more preferably in the range of 2 to 8% by mass, more preferably in the range of 3 to 7% by mass, based on the mass of the zeolite material contained in the aqueous mixture prepared in step (i).
[0144] Preferably, 98 to 100% by mass, more preferably 99 to 100% by mass, more preferably 99.5 to 100% by mass, more preferably 99.9 to 100% by mass of the aqueous mixture prepared in step (i) consists of water, the copper-containing zeolitic material, and a copper source other than the copper-containing zeolitic material. Alternatively, it is preferred that 98 to 100% by mass, more preferably 99 to 100% by mass, more preferably 99.5 to 100% by mass, more preferably 99.9 to 100% by mass of the aqueous mixture prepared in step (i) consists of water, the copper-containing zeolitic material, a copper source other than the copper-containing zeolitic material, and a precursor of the acidic component as defined above.
[0145] As a further alternative, it is preferred that from 98 to 100% by weight, more preferably from 99 to 100% by weight, more preferably from 99.5 to 100% by weight, more preferably from 99.9 to 100% by weight of the aqueous mixture prepared in step (i) consists of water, the copper-containing zeolitic material, a source of copper other than the copper-containing zeolitic material, a non-zeolitic acidic material as defined above, preferably one or more acids as defined above and optionally a precursor of an acidic component as defined above.
[0146] Regarding step (i), this is (i.1) preparing a first mixture comprising water and a source of copper other than a copper-containing zeolitic material; (i.2) milling the first mixture, more preferably until the particles of the first mixture have a Dv90 in the range of 0.5 to 20 micrometers (Dv90 is determined as described in Reference Example 3), optionally adding a precursor of an acidic component as defined above; (i.3) preparing a second mixture comprising water and a zeolitic material comprising copper; (i.4) mixing the second mixture obtained in step (i.3) with the first mixture obtained in step (i.1), more preferably in step (i.2); It is preferred that the compound contains
[0147] Preferably, 90-100% by mass, more preferably 95-100% by mass, more preferably 98-100% by mass of the source of copper other than the copper-containing zeolitic material is present in undissolved state in the mixture prepared in step (i.1).
[0148] The grinding in step (i.2) is preferably carried out until the particles of the first mixture have a Dv90 in the range of 4 to 15 micrometers, more preferably in the range of 6 to 12 micrometers, where Dv90 is determined as described in Reference Example 3.
[0149] With regard to step (i.4), it is preferred that this further comprises milling the mixture obtained in step (i.4), more preferably until the particles of said mixture have a Dv90 in the range of 0.5 to 20 micrometers, more preferably in the range of 2 to 15 micrometers, more preferably in the range of 2 to 10 micrometers, wherein Dv90 is determined as described in Reference Example 3.
[0150] The drying in step (ii) is preferably carried out in a gas atmosphere having a temperature in the range of 100 to 200° C., more preferably in the range of 120 to 140° C., the gas atmosphere more preferably containing oxygen.
[0151] For drying according to step (ii), it is preferred that this is carried out in a gas atmosphere for a duration in the range of 0.25 to 3 hours, more preferably in the range of 0.5 to 1.5 hours, the gas atmosphere more preferably containing oxygen.
[0152] For the calcination according to step (iii), it is preferred to carry this out in a gas atmosphere having a temperature in the range of 300-900° C., more preferably in the range of 400-500° C., the gas atmosphere more preferably containing oxygen.
[0153] For the calcination according to step (iii), it is preferred that this is carried out for a duration ranging from 0.5 to 8 hours, more preferably ranging from 1.5 to 3 hours, in a gas atmosphere, which more preferably contains oxygen.
[0154] It is preferred that the mass ratio of copper (calculated as CuO) contained in the zeolitic material obtained in step (iii) to copper (calculated as CuO) contained in the zeolitic material contained in the mixture from step (i) is in the range of 1.5:1 to 10:1, more preferably in the range of 2:1 to 5:1, more preferably in the range of 2:1 to 4:1.
[0155] Preferably, the process for preparing a zeolitic material having framework-type CHA and containing copper comprises steps (i), (ii) and (iii).
[0156] The present invention further relates to a zeolitic material having a framework-type CHA and comprising copper, preferably a zeolitic material having a framework-type CHA and comprising copper according to the invention, which is obtainable or can be obtained by the method according to the invention.
[0157] The present invention further relates to the use of a zeolitic material having framework CHA and containing copper according to the invention as a catalyst or catalytic article, preferably for the selective catalytic reduction of nitrogen oxides.
[0158] In the present invention, the term "based on the weight of the zeolite material" refers to the weight of the zeolite material alone, meaning that it does not include copper. Further, in the present invention, the term "based on the weight of the chabazite" refers to the weight of the chabazite alone, meaning that it does not include copper.
[0159] Furthermore, in the present invention, the term "inner wall surface" should be understood as the "bare" or "bare" or "blank" surface of the wall, i.e., the surface of the wall is in an untreated state and consists of the wall material, except for unavoidable impurities that may contaminate the surface.
[0160] Furthermore, in the present invention, the term "X is one or more of A, B, and C" is understood to disclose either that X is A, or B, or C, or A and B, or A and C, or B and C, or A and B and C, where X is a given feature and each of A, B, and C represents a specific realization of said feature. In this regard, it should be noted that a person skilled in the art can translate the above abstract terms into concrete examples, such as when X is a chemical element and A, B, and C are specific elements such as Li, Na, and K, or when X is a temperature and A, B, and C are specific temperatures such as 10°C, 20°C, and 30°C. In this regard, it is further noted that the skilled person may extend the above terminology to a less specific realization of said feature, e.g. "X is one or more of A and B," disclosing either X is A, or B, or A and B, or a more specific realization of said feature, e.g. "X is one or more of A, B, C, and D," disclosing either X is A, or B, or C, or D, or A and B, or A and C, or A and D, or B and C, or B and D, or C and D, or A and B and C, or A and B and D, or B and C and D, or A and B and C and D.
[0161] The present invention is further described by the first set of embodiments below, and the combination of embodiments resulting from the dependent references and back references as shown. Please note that in each instance where a range of embodiments is mentioned, especially in the context of a term such as "the method according to any one of embodiments 1 to 4", it means that all the embodiments in this range are clearly disclosed to those skilled in the art, that is, the wording of this term is understood by those skilled in the art to be synonymous with "the method according to any one of embodiments 1, 2, 3, and 4". The first set of embodiments below may be combined with any one of the second set of embodiments and the third set of embodiments below.
[0162] 1. A method for producing a catalyst comprising a copper-containing zeolitic material, comprising: (i) preparing an aqueous mixture comprising water, a copper-containing zeolitic material, a source of copper other than a copper-containing zeolitic material, and a non-zeolitic acidic material selected from the group consisting of alumina, silica, titania, zirconia, ceria, mixed oxides comprising one or more of Al, Si, Ti, Zr and Ce, and mixtures of two or more of these; (ii) disposing the mixture from step (i) on a surface of an interior wall of a substrate having an inlet end, an outlet end, a substrate axial length extending from said inlet end to said outlet end, and a plurality of passages extending through the substrate and defined by the interior wall of the substrate, and optionally drying the substrate on which the mixture is disposed; (iii) calcining the substrate obtained in step (ii) The method includes:
[0163] 2. The copper-containing zeolite material contained in the aqueous mixture prepared in step (i) is ABW, ACO, AEI, AEL, AEN, AET, AFG, AFI, AFN, AFO, AFR, AFS, AFT, AFV, AFX, AFY, AHT, ANA, APC, APD, AST, ASV, ATN, ATO, ATS, ATT, ATV, AVL, AWO, AWW. , BCT, BEA, BEC, BIK, BOF, BOG, BOZ, BPH, BRE, BSV, CAN, CAS, CDO, CFI, CGF, CGS, CHA, -CHI, -CLO, CON, CSV, CZP, DAC, DDR, DFO, DFT, DOH, DON, EAB, EDI, EEI, EMT, EON, EPI, ERI, ESV, ETR, EUO, * -EWT, EZT, FAR, FAU, FER, FRA, GIS, GIU, GME, GON, GOO, HEU, IFO, IFR, -IFU, IFW, IFY, IHW, IMF, IRN, IRR, -IRY, ISV, ITE, ITG, ITH, *-ITN, ITR, ITT, -ITV, ITW, IWR, IWS, IWV, IWW, JBW, JNT, JOZ, JRY, JSN, JSR, JST, JSW, KFI, LAU, LEV , LIO, -LIT, LOS, LOV, LTA, LTF, LTJ, LTL, LTN, MAR, MAZ, MEI, MEL, MEP, MER, MFI, MFS, MON, MOR, MOZ, * MRE, MSE, MSO, MTF, MTN, MTT, MTW, MVY, MWF, MWW, NAB, NAT, NES, NON, NPO, NPT, NSI, OBW, OFF, OKO, OSI, OSO, OWE, -PAR, PAU, PCR, PHI, PON, PO S, PSI, PUN, RHO, -RON, RRO, RSN, RTE, RTH, RUT, RWR, RWY, SAF, SAO, SAS, SAT, SAV, SBE, SBN, SBS, SBT, SEW, SFE, SFF, SFG, SFH, SFN, SFO, SFS, * SFV, SFW, SGT, SIV, SOD, SOF, SOS, SSF, * -SSO, SSY, STF, STI, * 2. The method according to embodiment 1, wherein the zeolitic material comprising copper contained in the aqueous mixture prepared in step (i) has a framework type selected from the group consisting of STO, STT, STW, -SVR, SVV, SZR, TER, THO, TOL, TON, TSC, TUN, UEI, UFI, UOS, UOV, UOZ, USI, UTL, UWY, VET, VFI, VNI, VSV, WEI, -WEN, YUG, ZON, mixtures of two or more thereof, and mixed types of two or more thereof, preferably a framework type selected from the group consisting of CHA, AEI, RTH, LEV, DDR, KFI, ERI, AFX, mixtures of two or more thereof, and mixed types of two or more thereof, more preferably a framework type selected from the group consisting of CHA, AEI, RTH, AFX, mixtures of two or more thereof, and mixed types of two or more thereof, more preferably a framework type selected from the group consisting of CHA and AEI,
[0164] 3. The method according to embodiment 2, wherein 95-100% by mass, preferably 98-100% by mass, more preferably 99-100% by mass of the framework structure of the zeolitic material consists of Si, Al and O, and the molar ratio of Si to Al in the framework structure, calculated as molar SiO2:Al2O3, is preferably in the range of 2:1 to 50:1, more preferably in the range of 5:1 to 45:1, more preferably in the range of 10:1 to 35:1, more preferably in the range of 16:1 to 28:1, more preferably in the range of 16:1 to 19:1 or more preferably in the range of 23:1 to 27:1.
[0165] 4. The method according to any one of the preceding claims, wherein the zeolitic material, preferably having framework type CHA, contained in the aqueous mixture prepared in step (i) has an average crystallite size, as determined by scanning electron microscopy, of at least 0.1 micrometer, preferably in the range of 0.1 to 3.0 micrometers, more preferably in the range of 0.3 to 1.5 micrometers, more preferably in the range of 0.4 to 1.0 micrometers.
[0166] 5. The method according to any one of embodiments 1 to 4, wherein the amount of copper (calculated as CuO) contained in the zeolitic material contained in the aqueous mixture prepared in step (i) is in the range of 0.05 to 3.5% by mass, preferably in the range of 0.1 to 3% by mass, more preferably in the range of 0.2 to 2% by mass, more preferably in the range of 0.5 to 1.75% by mass, more preferably in the range of 1 to 1.75% by mass, or more preferably in the range of 1.9 to 2.5% by mass, based on the weight of the zeolitic material contained in the aqueous mixture prepared in step (i).
[0167] 6. The method according to any one of the preceding claims, wherein the source of copper other than the copper-containing zeolitic material contained in the aqueous mixture prepared in step (i) is selected from the group consisting of copper acetate, copper nitrate, copper sulfate, copper formate, copper oxide, and mixtures of two or more thereof, preferably selected from the group consisting of copper acetate, copper oxide, and mixtures thereof, more preferably copper oxide, more preferably CuO.
[0168] 7. The method according to any one of the preceding embodiments, wherein the aqueous mixture prepared in step (i) comprises a source of copper other than the copper-containing zeolitic material in an amount, calculated as CuO, in the range of 0.1 to 14% by weight, more preferably in the range of 0.5 to 12% by weight, preferably in the range of 1 to 10% by weight, more preferably in the range of 1.5 to 5.0% by weight, more preferably in the range of 1.5 to 4.5% by weight, based on the weight of the zeolitic material contained in the aqueous mixture prepared in step (i).
[0169] 8. The method of embodiment 7, wherein the aqueous mixture prepared in step (i) comprises a source of copper other than the copper-containing zeolitic material in an amount in the range of 2.0 to 4.0 wt. %, calculated as CuO, based on the weight of the zeolitic material contained in the aqueous mixture prepared in step (i).
[0170] 9. The non-zeolitic acidic material contained in the aqueous mixture prepared in step (i) is selected from the group consisting of alumina, silica, titania, mixed oxides containing one or more of Al, Si, and Ti, and mixtures of two or more of these, preferably selected from the group consisting of alumina, silica, mixed oxides containing one or more of Al and Si, and mixtures of two or more of these, more preferably a mixture of alumina and silica; The method according to any one of the first to eighth embodiments, wherein the mixture of alumina and silica is more preferably 80 to 99% by mass, more preferably 85 to 98% by mass, more preferably 90 to 98% by mass, of alumina, and more preferably 1 to 20% by mass, more preferably 2 to 15% by mass, more preferably 2 to 10% by mass, of the mixture of alumina and silica is silica.
[0171] 10. The method according to any one of the preceding embodiments, wherein the aqueous mixture prepared in step (i) comprises non-zeolitic acidic material in an amount in the range of 2 to 20% by weight, preferably in the range of 5 to 15% by weight, more preferably in the range of 7 to 13% by weight, based on the weight of the zeolitic material contained in the aqueous mixture prepared in step (i).
[0172] 11. The method according to any one of the preceding embodiments, wherein in the aqueous mixture prepared in step (i), 10 to 90% by weight of the aqueous mixture is made up of water, preferably 40 to 85% by weight, more preferably 55 to 80% by weight.
[0173] 12. The aqueous mixture prepared in step (i) further comprises a precursor of an acidic component, the precursor being preferably one or more of an aluminum salt, a silicon salt, a zirconium salt, and a titanium salt, more preferably one or more of a zirconium salt and an aluminum salt, more preferably a zirconium salt, more preferably zirconium acetate; 12. The method according to any one of the preceding embodiments, wherein in the aqueous mixture prepared in step (i), the amount of precursor, calculated as oxide, preferably alumina, silica, zirconia or titania, preferably the amount of zirconium salt, calculated as ZrO2, is in the range of 1 to 10% by weight, more preferably in the range of 2 to 8% by weight, more preferably in the range of 3 to 7% by weight, based on the weight of the zeolitic material contained in the aqueous mixture prepared in step (i).
[0174] 13. The aqueous mixture prepared in step (i) further comprises particles of a carbon-containing additive; the carbon-containing additive contained in the aqueous mixture prepared in step (i) is preferably one or more of graphite, synthetic graphite, carbon black, graphene, diamond, fullerene, carbon nanotube, and amorphous carbon, more preferably one or more of graphite, synthetic graphite, graphene, fullerene, carbon nanotube, and amorphous carbon, more preferably one or more of graphite, synthetic graphite, and graphene, more preferably one or more of graphite and synthetic graphite, and / or the particles of the carbon-containing additive contained in the aqueous mixture prepared in step (i) preferably have a Dv50 in the range of 0.5 to 30 micrometers, more preferably in the range of 2 to 15 micrometers, more preferably in the range of 3 to 12 micrometers, more preferably in the range of 4 to 10 micrometers, more preferably in the range of 5 to 8 micrometers, the Dv50 being determined according to Reference Example 3 herein; and / or the particles of the carbon-containing additive contained in the aqueous mixture prepared in step (i) preferably have a Dv90 in the range of 4 to 60 micrometers, more preferably in the range of 6 to 30 micrometers, more preferably in the range of 8 to 20 micrometers, more preferably in the range of 9 to 14 micrometers, more preferably in the range of 10 to 13 micrometers, the Dv90 being determined according to Reference Example 3 herein; and / or 13. The method according to any one of the preceding embodiments, wherein the aqueous mixture prepared in step (i) preferably comprises particles of the carbon-containing additive in an amount in the range of 2 to 40% by weight, more preferably in the range of 4 to 30% by weight, more preferably in the range of 5 to 25% by weight, more preferably in the range of 5.5 to 15% by weight, based on the weight of the zeolitic material and the non-zeolitic acidic material in the aqueous mixture prepared in step (i).
[0175] 14. The method of any one of the preceding claims, wherein the aqueous mixture prepared in step (i) further comprises one or more additional non-zeolitic acidic materials, the one or more non-zeolitic acidic materials being selected from the group consisting of alumina, silica, titania, zirconia, ceria, mixed oxides comprising one or more of Al, Si, Ti, Zr and Ce, and mixtures of two or more thereof.
[0176] 15. The method according to any one of the preceding embodiments, wherein the aqueous mixture prepared in step (i) further comprises one or more acids, preferably two acids, more preferably two organic acids, more preferably tartaric acid and acetic acid, preferably in an amount in the range of 0.1 to 2% by weight, preferably in the range of 0.2 to 1.5% by weight, more preferably in the range of 0.4 to 1.2% by weight, based on the weight of the zeolitic material contained in the aqueous mixture prepared in step (i).
[0177] 16. The method according to any one of the preceding embodiments, wherein 98-100% by weight, preferably 99-100% by weight, more preferably 99.5-100% by weight, more preferably 99.9-100% by weight of the aqueous mixture prepared in step (i) consists of water, a zeolitic material comprising copper, a source of copper other than a zeolitic material comprising copper, and a non-zeolitic acidic material selected from the group consisting of alumina, silica, titania, zirconia, ceria, mixed oxides comprising one or more of Al, Si, Ti, Zr and Ce, and mixtures of two or more of these, and preferably one or more acids as defined in embodiment 15.
[0178] 17. The method according to any one of the preceding embodiments, wherein 98-100%, preferably 99-100%, more preferably 99.5-100%, more preferably 99.9-100% by weight of the aqueous mixture prepared in step (i) consists of water, a zeolitic material comprising copper, a source of copper other than a zeolitic material comprising copper, and a non-zeolitic acidic material selected from the group consisting of alumina, silica, titania, zirconia, ceria, mixed oxides comprising one or more of Al, Si, Ti, Zr and Ce, and mixtures of two or more of these, a precursor of an acidic component as defined in embodiment 12, and one or more acids as defined in embodiment 15, preferably.
[0179] 18. Step (i) comprises: (i.1) preparing a first mixture comprising water and a source of copper other than a copper-containing zeolitic material; (i.2) preferably milling the first mixture, more preferably until the particles of the first mixture have a Dv90 in the range of 0.5 to 20 micrometers (Dv90 is determined as described in Reference Example 3); (i.3) optionally adding a precursor of an acidic component as defined above to the first mixture obtained by step (i.1), preferably step (i.2); (i.4) preparing a second mixture comprising water and a zeolitic material comprising copper; (i.5) mixing the second mixture obtained in step (i.4) with the first mixture obtained in step (i.1), preferably in step (i.2) or step (i.3), to obtain a third mixture; (i.6) preparing a fourth mixture comprising water and a non-zeolitic acidic material selected from the group consisting of alumina, silica, titania, zirconia, ceria, mixed oxides comprising one or more of Al, Si, Ti, Zr and Ce, and mixtures of two or more of these, and preferably an acid, more preferably an organic acid, more preferably tartaric acid; (i.7) mixing the fourth mixture obtained in step (i.6) with the third mixture obtained in step (i.5), preferably by adding an acid, more preferably an organic acid, more preferably acetic acid, and optionally by adding particles of a carbon-containing additive as defined in embodiment 13 prior to the acid. Including, 18. The method according to any one of the preceding embodiments, wherein step (i) optionally consists of steps (i.1) to (i.7).
[0180] 19. The method according to embodiment 18, wherein 90-100% by weight, preferably 93-99% by weight, more preferably 96-99% by weight, of the source of copper other than the copper-containing zeolitic material is present in undissolved form in the mixture prepared in step (i.1) and step (i.2).
[0181] 20. The method according to embodiment 18 or 19, wherein the grinding in step (i.2) is carried out until the particles of the first mixture have a Dv90 in the range of 4 to 15 micrometers, preferably in the range of 6 to 12 micrometers, wherein Dv90 is determined as described in Reference Example 3.
[0182] 21. The first mixture obtained in step (i.1), preferably in step (i.2), has a solids content in the range of 4 to 30% by weight, preferably in the range of 4 to 15% by weight, based on the weight of the first mixture; and / or 21. The method according to any one of embodiments 18 to 20, wherein the second mixture obtained in step (i.4) has a solids content in the range of 15 to 50% by weight, preferably in the range of 20 to 45% by weight, more preferably in the range of 30 to 40% by weight, based on the weight of the second mixture.
[0183] 22. The method according to any one of embodiments 18 to 21, wherein step (i.5) further comprises grinding the third mixture, preferably until the particles of the third mixture have a Dv90 in the range of 0.5 to 20 micrometers, more preferably in the range of 2 to 15 micrometers, more preferably in the range of 2 to 10 micrometers, wherein the Dv90 is determined as described in Reference Example 3.
[0184] 23. The method according to any one of embodiments 18 to 22, wherein the fourth mixture obtained in step (i.6) has a solids content in the range of 15 to 60% by weight, preferably in the range of 25 to 45% by weight, more preferably in the range of 28 to 40% by weight, based on the weight of the fourth mixture.
[0185] 24. The method according to any one of embodiments 18 to 23, wherein the aqueous mixture obtained in step (i), more preferably in step (i.7), has a solids content in the range of 15 to 50% by weight, preferably in the range of 20 to 45% by weight, more preferably in the range of 30 to 40% by weight, based on the weight of the aqueous mixture.
[0186] 25. The method according to any one of the preceding claims, wherein the placement of the mixture according to step (ii) is carried out by spraying the mixture onto the substrate or by immersing the substrate in the mixture, preferably by immersing the substrate in the mixture.
[0187] 26. The method according to any one of the preceding embodiments, wherein in step (ii), the mixture from step (i) is disposed over x% of the axial length of the substrate from the inlet end to the outlet end of the substrate, or from the outlet end to the inlet end of the substrate, where x is in the range of 80 to 100, preferably in the range of 90 to 100, more preferably in the range of 95 to 100, more preferably in the range of 98 to 100.
[0188] 27. The method according to any one of the preceding embodiments, wherein the substrate in step (ii) is a wall-flow filter substrate, preferably one or more of a cordierite wall-flow filter substrate, a silicon carbide wall-flow filter substrate and an aluminum titanate wall-flow filter substrate, preferably one or more of a silicon carbide wall-flow filter substrate and an aluminum titanate wall-flow filter substrate, more preferably a silicon carbide wall-flow filter substrate.
[0189] 28. The method according to any one of the preceding embodiments, wherein the substrate in step (ii) is a flow-through substrate, preferably one or more of a cordierite flow-through substrate, a silicon carbide flow-through substrate and an aluminum titanate flow-through substrate, more preferably one or more of a silicon carbide flow-through substrate and a cordierite flow-through substrate, more preferably a cordierite flow-through substrate.
[0190] 29. The method according to any one of the preceding embodiments, wherein the drying according to step (ii) is carried out in a gas atmosphere having a temperature in the range of 60 to 300° C., preferably in the range of 90 to 150° C., the gas atmosphere preferably comprising oxygen.
[0191] 30. The method according to any one of the preceding embodiments, wherein the drying according to step (ii) is carried out in a gas atmosphere for a duration in the range of 10 minutes to 4 hours, preferably in the range of 20 minutes to 3 hours, more preferably in the range of 50 minutes to 2.5 hours, and the gas atmosphere preferably contains oxygen.
[0192] 31. The arrangement according to step (ii) (ii.1) disposing a first portion of the mixture obtained in step (i) on a surface of an inner wall of a substrate, the inner wall of the substrate having an inlet end, an outlet end, a length along an axial direction of the substrate extending from the inlet end to the outlet end, and a plurality of passages extending through the substrate and defined by the inner wall of the substrate; and drying the substrate on which the first portion of the mixture is disposed; (ii.2) disposing a second portion of the mixture obtained in step (i) on the substrate on which the first portion of the mixture obtained in step (ii.1) is disposed, and optionally drying the substrate on which the first and second portions of the mixture are disposed. 31. The method of any one of the preceding claims, comprising:
[0193] 32. The method of embodiment 31, wherein the mixture obtained in step (i) is further diluted before the first portion of the mixture obtained in step (i) is disposed on the surface of the inner wall of the substrate by step (ii.1).
[0194] 33. The method of embodiment 31 or 32, wherein the mixture obtained in step (i) is further diluted before a second portion of the mixture obtained in step (i) is disposed on the surface of the inner wall of the substrate by step (ii.2).
[0195] 34. The method according to any one of embodiments 31 to 33, wherein in step (ii.1), a first portion of the mixture from step (i) is disposed over x1% of the axial length of the substrate from the inlet end to the outlet end, or from the outlet end to the inlet end, of the substrate, where x1 is in the range of 80 to 100, preferably in the range of 90 to 100, more preferably in the range of 95 to 100, more preferably in the range of 98 to 100.
[0196] 35. The method of embodiment 34, wherein step (ii.2) comprises disposing a second portion of the mixture from step (i) over x2% of the axial length of the substrate from the inlet end to the outlet end, or from the outlet end to the inlet end, of the substrate, where x2 is in the range of 80 to 100, preferably in the range of 90 to 100, more preferably in the range of 95 to 100, more preferably in the range of 98 to 100, and more preferably x2 is x1.
[0197] 36. The method according to any one of embodiments 31 to 35, wherein the drying according to step (ii.1) is carried out in a gas atmosphere having a temperature in the range of 60 to 300°C, preferably in the range of 90 to 150°C, and the gas atmosphere preferably contains oxygen.
[0198] 37. The method according to any one of embodiments 31 to 36, wherein the drying according to step (ii.1) is carried out in a gas atmosphere for a duration in the range of 10 minutes to 4 hours, preferably in the range of 20 minutes to 3 hours, more preferably in the range of 50 minutes to 2.5 hours, and the gas atmosphere preferably contains oxygen.
[0199] 38. The method according to any one of embodiments 31 to 37, wherein the drying according to step (ii.2) is carried out in a gas atmosphere having a temperature in the range of 60 to 300°C, preferably in the range of 90 to 150°C, and the gas atmosphere preferably contains oxygen.
[0200] 39. The method according to any one of embodiments 31 to 38, wherein the drying according to step (ii.2) is carried out in a gas atmosphere for a duration in the range of 10 minutes to 4 hours, preferably in the range of 20 minutes to 3 hours, more preferably in the range of 50 minutes to 2.5 hours, and the gas atmosphere preferably contains oxygen.
[0201] 40. The method according to any one of the preceding embodiments, wherein the calcination according to step (iii) is carried out in a gas atmosphere having a temperature in the range of 300 to 900° C., preferably in the range of 400 to 650° C., more preferably in the range of 400 to 500° C., or more preferably in the range of 550 to 600° C., and the gas atmosphere preferably contains oxygen.
[0202] 41. The method according to any one of the preceding embodiments, wherein the calcination according to step (iii) is carried out in a gas atmosphere for a duration in the range of 0.1 to 4 hours, preferably in the range of 0.5 to 2.5 hours, the gas atmosphere preferably comprising oxygen.
[0203] 42. The method according to any one of the preceding embodiments, wherein the mass ratio of copper (calculated as CuO) contained in the zeolitic material contained in the substrate obtained in step (iii) to copper (calculated as CuO) contained in the zeolitic material contained in the mixture from step (i) is in the range of 1.5:1 to 10:1, preferably in the range of 2:1 to 5:1, more preferably in the range of 2:1 to 4:1.
[0204] 43. The method of any one of embodiments 1 to 42, comprising steps (i), (ii) and (iii).
[0205] 44. A catalyst comprising a zeolitic material comprising copper, obtained or obtainable by the method according to any one of embodiments 1 to 43, preferably embodiment 43.
[0206] 45. The catalyst of embodiment 44, wherein the amount of copper contained in the catalyst, calculated as CuO, is in the range of 2 to 10% by weight, preferably in the range of 2.5 to 5.5% by weight, and more preferably in the range of 2.5 to 5% by weight, based on the weight of the zeolitic material.
[0207] 46. The catalyst according to embodiment 44 or 45, wherein 75 to 100% by weight, preferably 78 to 100% by weight, more preferably 80 to 100% by weight, of the copper contained in the catalyst is contained in the zeolitic material.
[0208] 47. The catalyst of any one of embodiments 44 to 46, wherein the amount of copper in the zeolite contained in the catalyst is greater than the amount of copper contained in the zeolitic material contained in the mixture from step (i).
[0209] 48. The catalyst is 0.8 to 2.6 g / in 3 in the range of 1.2 to 2.2 g / in 3 More preferably, the range is 1.5 to 2.2 g / in 3 48. The catalyst of any one of embodiments 44 to 47, comprising a zeolitic material at a loading in the range of
[0210] 49. The catalyst is 0.02 to 0.52 g / in 3 in the range of 0.1 to 0.42 g / in 3 More preferably, the range is 0.1 to 0.21 g / in 3 49. The catalyst of any one of embodiments 44 to 48, comprising a non-zeolitic acidic material at a loading in the range of
[0211] 50. The catalyst further comprises an acidic component, the acidic component being selected from the group consisting of alumina, silica, zirconia, titania, mixed oxides containing two or more of Si, Al, Zr and Ti, and mixtures of two or more of these, preferably selected from the group consisting of alumina, zirconia, mixed oxides of Al and Zr, and mixtures thereof, and the acidic component is more preferably zirconia; The catalyst is more preferably 0.2 to 0.26 g / in 3 More preferably, the range is 0.4 to 0.2 g / in 3 More preferably, the range is 0.06 to 0.14 g / in 3 50. The catalyst of any one of embodiments 44 to 49, comprising an acidic component at a loading in the range of
[0212] 51. The catalyst of any one of embodiments 44 to 50, comprising a coating disposed on a surface of an inner wall of the substrate, the coating comprising a zeolitic material comprising copper, a non-zeolitic acidic material, and optionally an acidic component as defined in embodiment 50.
[0213] 52. The catalyst according to any one of embodiments 44 to 51, exhibiting a NOx activity determined as defined in Example 2, which is higher than the NOx activity of a catalyst prepared in the same manner except for step (i) being replaced by step (I1), wherein step (I1) comprises the preparation of an aqueous mixture comprising water, a zeolitic material in H form, a source of copper, and a non-zeolitic acidic material selected from the group consisting of alumina, silica, titania, zirconia, ceria, mixed oxides comprising one or more of Al, Si, Ti, Zr and Ce, and mixtures of two or more of these; The amount of copper contained in the aqueous mixture prepared in step (I1), calculated as CuO, is equal to the amount of copper contained in the aqueous mixture prepared in step (i), which amount of copper contained in the aqueous mixture prepared in step (i) includes the amount of copper contained in the copper-containing zeolitic material used in step (i) and the amount of copper from the source of copper used in step (i).
[0214] 53. The catalyst according to any one of embodiments 44 to 52, having a NOx conversion activity, determined as defined in Example 2, which is higher than the NOx conversion activity of a catalyst comprising a zeolitic material comprising copper, other than a catalyst obtained or obtainable by the method according to any one of embodiments 1 to 43 under the same conditions and with the same loading.
[0215] 54. A catalyst, wherein the copper-containing zeolitic material is a zeolitic material according to any one of embodiments 1″ to 6″ and embodiment 29″ according to the set of third embodiments described herein below.
[0216] 55. The catalyst according to any one of embodiments 44 to 54, wherein 98 to 100% by weight, preferably 99 to 100% by weight, more preferably 99.5 to 100% by weight of the catalyst consists of a zeolitic material containing copper, and a non-zeolitic acidic material selected from the group consisting of alumina, silica, titania, zirconia, ceria, mixed oxides containing one or more of Al, Si, Ti, Zr and Ce, and mixtures of two or more of these, and a substrate; or 50. A catalyst comprising 98-100% by weight, preferably 99-100% by weight, more preferably 99.5-100% by weight of the catalyst consisting of a zeolitic material containing copper, and a non-zeolitic acidic material selected from the group consisting of alumina, silica, titania, zirconia, ceria, mixed oxides containing one or more of Al, Si, Ti, Zr and Ce, and mixtures of two or more of these, a substrate, and an acidic component as defined in embodiment 50.
[0217] 56. A method of using the catalyst according to any one of embodiments 44 to 55 for the selective catalytic reduction of nitrogen oxides.
[0218] 57. A method for selective catalytic reduction of nitrogen oxides, comprising: (1) providing an exhaust gas stream, preferably from a compression ignition engine; (2) passing the exhaust gas stream provided in (1) through the catalyst of any one of embodiments 44 to 55. A method comprising:
[0219] 58. A method according to any one of the preceding embodiments, wherein the aqueous mixture prepared by (i) is an aqueous mixture according to any one of the preceding embodiments 1' to 19' according to a set of the second embodiment described herein below.
[0220] 59. An exhaust gas treatment system for treating an exhaust gas stream exiting a compression ignition engine, the exhaust gas treatment system having an upstream end for introducing the exhaust gas stream into the exhaust gas treatment system, the exhaust gas treatment system comprising the catalyst of any one of embodiments 44 to 55 and one or more of a diesel oxidation catalyst, a selective catalytic reduction catalyst, an ammonia oxidation catalyst, a NOx trap, and a particulate filter.
[0221] 60. An exhaust gas treatment system as described in embodiment 59, comprising a diesel oxidation catalyst disposed downstream of the engine and upstream of the catalyst as described in any one of embodiments 44 to 55, optionally the diesel oxidation catalyst containing a NOx storage function.
[0222] 61. The exhaust gas treatment system of embodiment 60, further comprising one or more of a selective catalytic reduction catalyst and an ammonia oxidation catalyst disposed downstream of the catalyst of any one of embodiments 44 to 55.
[0223] 62. The exhaust gas treatment system of embodiment 60 or 61, further comprising a selective catalytic reduction catalyst disposed downstream of the diesel oxidation catalyst and upstream of the catalyst of any one of embodiments 44 to 55.
[0224] The invention is further described by the following second set of embodiments and combinations of embodiments resulting from the dependent and back references as indicated. The second set of embodiments may be combined with the first set of embodiments above.
[0225] 1'. An aqueous mixture comprising water, a copper-containing zeolitic material, a source of copper other than a copper-containing zeolitic material, and a non-zeolitic acidic material selected from the group consisting of alumina, silica, titania, zirconia, ceria, mixed oxides comprising one or more of Al, Si, Ti, Zr, and Ce, and mixtures of two or more of the foregoing.
[0226] 2'. ABW, ACO, AEI, AEL, AEN, AET, AFG, AFI, AFN, AFO, AFR, AFT, AFV, AFV X、AFY、AHT、ANA、APC、APD、AST、ASV、ATN、ATO、ATS、ATT、ATV、AVL、AWO、AWW、BCT、BEA、BE C、BIK、BOF、BOG、BOZ、BPH、BRE、BSV、CAN、CAS、CDO、CFI、CGF、CGS、CHA、-CHI、-CLO、CON、 CSV, CZP, DAC, DDR, DFO, DFT, DOH, DON, EAB, EDI, EEI, EMT, EON, EPI, ERI, ESV, ETR, EUO. * -EWT、EZT、FAR、FAU、FER、FRA、GIS、GIU、GME、GON、GOO、HEU、IFO、 IFR、-IFU、IFW、IFY、IHW、IMF、IRN、IRR、-IRY、ISV、ITE、ITG、ITH、 * -ITN、ITR、ITT、-ITV、ITW、IWR、IWS、IWV、IWW、JBW、JNT、JOZ、JRY、JSN、JSR、JST、JSW、LAKFI、LEV 、LIO、-LIT、LOS、LOV、LTA、LTF、LTJ、LTL、LTN、MAR、MAZ、MEI、MEL、MEP、MER、MFI、MFS、MON、MOR、MOZ * MRE、MSE、MSO、MTF、MTN、MTT、MTW、MVY、MWF、MWW、NAB、NAT、NES、NON、N PO、NPT、NSI、OBW、OFF、OKO、OSI、OSO、OWE、-PAR、PAU、PCR、PHI、PON、PO S、PSI、PUN、RHO、-RON、RRO、RSN、RTE、RTH、RUT、RWR、RWY、SAF、SAO、SA S、SAT、SAV、SBE、SBN、SBS、SBT、SEW、SFE、SFF、SFG、SFH、SFN、SFO、SFS、 * SFV、SFW、SGT、SIV、SOD、SOF、SOS、SSF、 * -SSO、SSY、STF、STI、 *The mixture according to embodiment 1', having a framework type selected from the group consisting of STO, STT, STW, -SVR, SVV, SZR, TER, THO, TOL, TON, TSC, TUN, UEI, UFI, UOS, UOV, UOZ, USI, UTL, UWY, VET, VFI, VNI, VSV, WEI, -WEN, YUG, ZON, mixtures of two or more thereof, and mixed types of two or more thereof, preferably a framework type selected from the group consisting of CHA, AEI, RTH, LEV, DDR, KFI, ERI, AFX, mixtures of two or more thereof, and mixed types of two or more thereof, more preferably a framework type selected from the group consisting of CHA, AEI, RTH, AFX, mixtures of two or more thereof, and mixed types of two or more thereof, more preferably a framework type selected from the group consisting of CHA and AEI, and the copper-containing zeolitic material has framework type CHA.
[0227] 3'. The mixture according to embodiment 2', wherein 95-100% by mass, preferably 98-100% by mass, more preferably 99-100% by mass of the framework structure of the zeolitic material consists of Si, Al and O, and the molar ratio of Si to Al in the framework structure, calculated as molar SiO2:Al2O3, is preferably in the range of 2:1 to 50:1, more preferably in the range of 5:1 to 45:1, more preferably in the range of 10:1 to 35:1, more preferably in the range of 16:1 to 28:1, more preferably in the range of 16:1 to 19:1, or more preferably in the range of 23:1 to 27:1.
[0228] 4'. The mixture of any one of embodiments 1' to 3', wherein the zeolitic material, preferably having framework CHA, has an average crystallite size, as determined by scanning electron microscopy, of at least 0.1 micrometers, preferably in the range of 0.1 to 3.0 micrometers, more preferably in the range of 0.3 to 1.5 micrometers, more preferably in the range of 0.4 to 1.0 micrometers.
[0229] 5'. The mixture according to any one of embodiments 1' to 4', wherein the amount of copper contained in the zeolitic material, calculated as CuO, is in the range of 0.05 to 3.5% by weight, preferably in the range of 0.1 to 3% by weight, more preferably in the range of 0.2 to 2% by weight, more preferably in the range of 0.5 to 1.75% by weight, more preferably in the range of 1 to 1.75% by weight, or more preferably in the range of 1.9 to 2.5% by weight, based on the weight of the zeolitic material.
[0230] 6'. The mixture of any one of embodiments 1' to 5', wherein the source of copper other than the copper-containing zeolitic material is selected from the group consisting of copper acetate, copper nitrate, copper sulfate, copper formate, copper oxide, and mixtures of two or more thereof, preferably selected from the group consisting of copper acetate, copper oxide, and mixtures of two or more thereof, more preferably copper oxide, more preferably CuO.
[0231] 7. The mixture according to any one of embodiments 1' to 6', wherein the aqueous mixture comprises a source of copper other than the copper-containing zeolitic material in an amount in the range of 0.1 to 14% by weight, preferably in the range of 0.5 to 12% by weight, preferably in the range of 1 to 10% by weight, more preferably in the range of 1.5 to 5.0% by weight, calculated as CuO, based on the weight of the zeolitic material.
[0232] 8'. The mixture of embodiment 7', wherein the aqueous mixture comprises a source of copper other than the copper-containing zeolitic material in an amount in the range of 1.5 to 4 weight percent, calculated as CuO, based on the weight of the zeolitic material.
[0233] 9'. The non-zeolitic acidic material is selected from the group consisting of alumina, silica, titania, mixed oxides containing one or more of Al, Si, and Ti, and mixtures of two or more of these, preferably alumina, silica, mixed oxides containing one or more of Al and Si, and mixtures of two or more of these, more preferably a mixture of alumina and silica; More preferably, the mixture of alumina and silica comprises 80 to 99% by mass, more preferably 85 to 98% by mass, more preferably 90 to 98% by mass of alumina, and more preferably, the mixture of alumina and silica comprises 1 to 20% by mass, more preferably 2 to 15% by mass, more preferably 2 to 10% by mass of silica.
[0234] 10'. The mixture of any one of embodiments 1' to 9', wherein the aqueous mixture comprises non-zeolitic acidic material in an amount in the range of 2 to 20% by weight, preferably in the range of 5 to 15% by weight, more preferably in the range of 7 to 13% by weight, based on the weight of the zeolitic material.
[0235] 11'. The mixture according to any one of embodiments 1' to 10', wherein 10 to 90% by weight, preferably 40 to 85% by weight, more preferably 55 to 80% by weight of the aqueous mixture is water.
[0236] 12'. The mixture of any one of embodiments 1' to 11', further comprising a precursor of an acidic component, the precursor being preferably one or more of an aluminum salt, a silicon salt, a zirconium salt, and a titanium salt, more preferably one or more of a zirconium salt and an aluminum salt, more preferably a zirconium salt, more preferably zirconium acetate; The mixture, wherein the amount of precursor, calculated as oxide, preferably alumina, silica, zirconia or titania, more preferably the amount of zirconium salt, calculated as ZrO2, in the aqueous mixture is in the range of 1 to 10% by weight, preferably in the range of 2 to 8% by weight, more preferably in the range of 3 to 7% by weight, based on the weight of the zeolitic material.
[0237] 13'. The mixture of any one of embodiments 1' to 12', further comprising particles of a carbon-containing additive; The carbon-containing additive contained in the mixture is preferably one or more of graphite, synthetic graphite, carbon black, graphene, diamond, fullerene, carbon nanotube, and amorphous carbon, more preferably one or more of graphite, synthetic graphite, graphene, fullerene, carbon nanotube, and amorphous carbon, more preferably one or more of graphite, synthetic graphite, and graphene, more preferably one or more of graphite and synthetic graphite, and / or the particles of the carbon-containing additive contained in the mixture preferably have a Dv50 in the range of 0.5 to 30 micrometers, more preferably in the range of 2 to 15 micrometers, more preferably in the range of 3 to 12 micrometers, more preferably in the range of 4 to 10 micrometers, more preferably in the range of 5 to 8 micrometers, the Dv50 being determined according to Reference Example 3 herein; and / or the particles of the carbon-containing additive contained in the mixture preferably have a Dv90 in the range of 4 to 60 micrometers, more preferably in the range of 6 to 30 micrometers, more preferably in the range of 8 to 20 micrometers, more preferably in the range of 9 to 14 micrometers, more preferably in the range of 10 to 13 micrometers, the Dv90 being determined according to Reference Example 3 herein; and / or The mixture comprises particles of a carbon-containing additive in an amount in the range of 2 to 40% by weight, preferably in the range of 4 to 30% by weight, more preferably in the range of 5 to 25% by weight, more preferably in the range of 5.5 to 15% by weight, based on the weight of the zeolitic material and non-zeolitic acidic material in the mixture.
[0238] 14'. The mixture of any one of embodiments 1' to 13', wherein the aqueous mixture further comprises one or more additional non-zeolitic acidic materials selected from the group consisting of alumina, silica, titania, zirconia, ceria, mixed oxides comprising one or more of Al, Si, Ti, Zr, and Ce, and mixtures of two or more thereof.
[0239] 15'. The mixture according to any one of embodiments 1' to 14', further comprising one or more acids, preferably two acids, more preferably two organic acids, more preferably tartaric acid and acetic acid, preferably in an amount in the range of 0.1 to 2% by weight, more preferably in the range of 0.2 to 1% by weight, based on the weight of the zeolitic material.
[0240] 16'. The mixture of any one of embodiments 1' to 15', having a solids content in the range of 15 to 50% by weight, preferably in the range of 20 to 45% by weight, more preferably in the range of 30 to 40% by weight, based on the weight of the mixture.
[0241] 17'. The mixture according to any one of embodiments 1' to 16', wherein 98 to 100% by weight, preferably 99 to 100% by weight, more preferably 99.5 to 100% by weight, more preferably 99.9 to 100% by weight of the mixture consists of water, a zeolitic material containing copper, a source of copper other than a zeolitic material containing copper, and a non-zeolitic acidic material selected from the group consisting of alumina, silica, titania, zirconia, ceria, mixed oxides containing one or more of Al, Si, Ti, Zr and Ce, and mixtures of two or more thereof, and one or more acids, preferably as defined in embodiment 15'.
[0242] 18'. The mixture according to any one of embodiments 1' to 16', wherein 98% to 100%, preferably 99% to 100%, more preferably 99.5% to 100%, more preferably 99.9% to 100%, by weight of the mixture consists of water, a zeolitic material containing copper, a source of copper other than a zeolitic material containing copper, and a non-zeolitic acidic material selected from the group consisting of alumina, silica, titania, zirconia, ceria, mixed oxides containing one or more of Al, Si, Ti, Zr and Ce, and mixtures of two or more thereof, a precursor of an acidic component as defined in embodiment 12', and one or more acids as defined in embodiment 15'.
[0243] 19'. The mixture of any one of embodiments 1' to 18', wherein the mixture is an aqueous mixture prepared in step (i) of the method of any one of embodiments 1 to 44 of the first set of embodiments above.
[0244] 20'. (i.1) preparing a first mixture comprising water and a source of copper other than a copper-containing zeolitic material; (i.2) optionally a precursor of the acidic component as defined in embodiment 12' in the first mixture obtained by step (i.1), (i.3) preparing a second mixture comprising water and a zeolitic material comprising copper; (i.4) mixing the second mixture obtained in step (i.3) with the first mixture obtained in step (i.1) or in step (i.2) to obtain a third mixture; (i.5) preparing a fourth mixture comprising water and a non-zeolitic acidic material selected from the group consisting of alumina, silica, titania, zirconia, ceria, mixed oxides comprising one or more of Al, Si, Ti, Zr and Ce, and mixtures of two or more of these, and preferably an acid, more preferably an organic acid, more preferably tartaric acid; (i.6) mixing the fourth mixture obtained in step (i.5) with the third mixture obtained in step (i.4), preferably by adding an acid, more preferably an organic acid, more preferably acetic acid, and optionally by adding particles of a carbon-containing additive as defined in embodiment 13' prior to the acid, A method for preparing a mixture according to any one of embodiments 1' to 19', comprising:
[0245] 21'. The method of embodiment 20', wherein 90-100%, preferably 95-100%, more preferably 96-99%, by weight of the source of copper other than the copper-containing zeolitic material is present in the mixture prepared in (i.1) in undissolved state.
[0246] 22'. The method of embodiment 20' or 21', wherein step (i.1) further comprises grinding the first mixture, preferably until the particles of the first mixture have a Dv90 in the range of 0.5 to 20 micrometers, more preferably in the range of 4 to 15 micrometers, more preferably in the range of 6 to 12 micrometers, wherein the Dv90 is determined as described in Reference Example 3.
[0247] 23'. The method according to any one of embodiments 20' to 22', wherein the first mixture obtained in step (i.1) has a solids content in the range of 4 to 30% by weight, preferably in the range of 4 to 15% by weight, based on the weight of the first mixture.
[0248] 24'. The method according to any one of embodiments 20' to 23', wherein the second mixture obtained in step (i.3) has a solids content in the range of 15 to 50% by weight, preferably in the range of 20 to 45% by weight, more preferably in the range of 30 to 40% by weight, based on the weight of the second mixture.
[0249] 25'. The method according to any one of embodiments 20' to 24', wherein step (i.4) further comprises grinding the third mixture, preferably until the particles of the third mixture have a Dv90 in the range of 0.5 to 20 micrometers, more preferably in the range of 2 to 15 micrometers, more preferably in the range of 2 to 10 micrometers, wherein the Dv90 is determined as described in Reference Example 3.
[0250] 26'. The method according to any one of embodiments 20' to 25', wherein the fourth mixture obtained in step (i.5) has a solids content in the range of 15 to 50% by weight, preferably in the range of 20 to 45% by weight, more preferably in the range of 28 to 40% by weight, based on the weight of the fourth mixture.
[0251] 27'. The method according to any one of embodiments 20' to 26', wherein the aqueous mixture obtained in step (i), more preferably in step (i.6), has a solids content in the range of 15 to 50% by weight, preferably in the range of 20 to 45% by weight, more preferably in the range of 30 to 40% by weight, based on the weight of the aqueous mixture.
[0252] 28'. The method according to any one of embodiments 20' to 27', comprising steps (i.1), (i.2), (i.3), (i.4), (i.5) and (i.6).
[0253] 29'. An aqueous mixture obtained or obtainable by the method according to any one of embodiments 20' to 28', preferably embodiment 28'.
[0254] 30'. A method of using the aqueous mixture according to any one of embodiments 1' to 19' and embodiment 29' for the preparation of a catalyst, preferably a selective catalytic reduction catalyst.
[0255] 31'. Use of the aqueous mixture according to any one of embodiments 1' to 19' and embodiment 29' 2. A method for preparing a catalyst, preferably a selective catalytic reduction catalyst, comprising:
[0256] The present invention is further described by the following third set of embodiments and combinations of embodiments resulting from the dependent and back references as indicated. The third set of embodiments may be combined with any one of the first set of embodiments and the second set of embodiments above.
[0257] 1”. A zeolitic material having framework type CHA and containing copper, wherein the framework structure of the zeolitic material contains Si, Al, and O and is determined as described in Example 12, as follows: Maximum value: 930~975cm -1 in the range of 935 to 970 cm -1 More preferably, in the range of 945 to 965 cm -1 a first absorption peak (P1) having a range of Maximum value: 880~920cm -1 in the range of 885 to 915 cm -1 More preferably, the range is 890 to 910 cm -1 a second absorption peak (P2) having a range of The IR spectrum includes A zeolite material, in which the ratio of the peak area of the first absorption peak to the peak area of the second absorption peak, P1:P2, is in the range of 0.2:1 to 1.55:1, preferably in the range of 0.5:1 to 1.53:1, more preferably in the range of 1.05:1 to 1.53:1, more preferably in the range of 1.07:1 to 1.45:1, more preferably in the range of 1.10:1 to 1.40:1, more preferably in the range of 1.12:1 to 1.35:1, more preferably in the range of 1.15:1 to 1.32:1.
[0258] 2". The zeolitic material according to embodiment 1", wherein 95 to 100 mass%, preferably 98 to 100 mass%, more preferably 99 to 100 mass% of the framework structure of the zeolitic material is composed of Si, Al and O, and the molar ratio of Si to Al in the framework structure, calculated as molar SiO2:Al2O3, is preferably in the range of 2:1 to 50:1, more preferably in the range of 5:1 to 45:1, more preferably in the range of 10:1 to 35:1, more preferably in the range of 16:1 to 28:1, more preferably in the range of 16:1 to 19:1, or more preferably in the range of 23:1 to 27:1.
[0259] 3". The zeolitic material according to embodiment 1" or 2", wherein the zeolitic material has an average crystallite size, as determined by scanning electron microscopy, of at least 0.1 micrometers, preferably in the range of 0.1 to 3.0 micrometers, more preferably in the range of 0.3 to 1.5 micrometers, more preferably in the range of 0.4 to 1.0 micrometers.
[0260] 4". The zeolitic material according to any one of embodiments 1" to 3", wherein the amount of copper contained in the zeolitic material, calculated as CuO, is in the range of 1 to 10% by weight, preferably in the range of 1.5 to 5% by weight, and more preferably in the range of 1.5 to 4% by weight, based on the weight of the zeolitic material.
[0261] 5”. Peak area of the first absorption peak, 890~965cm -1 to the total peak area of all absorption peaks having a maximum in the wavelength range of from 0.05:1 to 0.50:1, preferably in the range of from 0.08:1 to 0.5:1, more preferably in the range of from 0.1:1 to 0.5:1, more preferably in the range of from 0.15:1 to 0.49:1, more preferably in the range of from 0.25:1 to 0.48:1, more preferably in the range of from 0.30:1 to 0.45:1, more preferably in the range of from 0.40:1 to 0.45:1.
[0262] 6”. 400~800m 2 / g range, preferably 500 to 700m 2 The zeolitic material of any one of embodiments 1″ to 5″ has a BET specific surface area in the range of 0.1 to 0.2 nm / g, the BET specific surface area being determined as described in Reference Example 1.
[0263] 7". A process for preparing the zeolitic material according to any one of embodiments 1" to 6", comprising: (i) preparing an aqueous mixture comprising water, a zeolitic material having a framework CHA and containing copper, and a source of copper other than the copper-containing zeolitic material; (ii) optionally drying the mixture obtained in step (i); (iii) calcining the mixture obtained in step (i) or step (ii). A method comprising:
[0264] 8". The method according to embodiment 7", wherein 95-100% by mass, preferably 98-100% by mass, more preferably 99-100% by mass of the framework structure of the zeolitic material consists of Si, Al and O, and the molar ratio of Si to Al in the framework structure, calculated as molar SiO2:Al2O3, is preferably in the range of 2:1 to 50:1, more preferably in the range of 5:1 to 45:1, more preferably in the range of 10:1 to 35:1, more preferably in the range of 16:1 to 28:1, more preferably in the range of 16:1 to 19:1 or more preferably in the range of 23:1 to 27:1.
[0265] 9". The method of embodiment 7" or 8", wherein the zeolitic material contained in the aqueous mixture prepared in step (i) has an average crystallite size, as determined by scanning electron microscopy, of at least 0.1 micrometer, preferably in the range of 0.1 to 3.0 micrometers, more preferably in the range of 0.3 to 1.5 micrometers, more preferably in the range of 0.4 to 1.0 micrometers.
[0266] 10". The method according to any one of embodiments 7" to 9", wherein the amount of copper contained in the zeolitic material contained in the aqueous mixture prepared in step (i), calculated as CuO, is in the range of 0.1 to 3% by weight, preferably in the range of 0.2 to 2% by weight, and more preferably in the range of 0.5 to 1.75% by weight, based on the weight of the zeolitic material contained in the aqueous mixture prepared in step (i).
[0267] 11". The method of any one of embodiments 7" to 10", wherein the source of copper other than the copper-containing zeolitic material is selected from the group consisting of copper acetate, copper nitrate, copper sulfate, copper formate, copper oxide, and mixtures of two or more thereof, preferably selected from the group consisting of copper acetate, copper oxide, and mixtures of two or more thereof, more preferably copper oxide, more preferably CuO.
[0268] 12". The method according to any one of embodiments 7" to 11", wherein the aqueous mixture prepared in step (i) comprises a source of copper other than the copper-containing zeolitic material in an amount in the range of 1 to 10% by weight, preferably in the range of 1.5 to 5% by weight, calculated as CuO, based on the weight of the zeolitic material contained in the aqueous mixture prepared in step (i).
[0269] 13". The method of embodiment 12", wherein the aqueous mixture prepared in step (i) comprises a source of copper other than the copper-containing zeolitic material in an amount in the range of 1.5 to 4.5% by weight, preferably in the range of 1.5 to 4% by weight, calculated as CuO, based on the weight of the zeolitic material contained in the aqueous mixture prepared in step (i).
[0270] 14". The method according to any one of embodiments 7" to 13", wherein in the aqueous mixture prepared in step (i), 10 to 90% by weight of the aqueous mixture consists of water, preferably 40 to 85% by weight, more preferably 55 to 80% by weight.
[0271] 15". The method of any one of embodiments 7" to 14", wherein the aqueous mixture prepared in step (i) further comprises a precursor of the acidic component, the precursor being preferably one or more of an aluminum salt, a silicon salt, a zirconium salt, and a titanium salt, more preferably one or more of a zirconium salt and an aluminum salt, more preferably a zirconium salt, more preferably zirconium acetate.
[0272] 16". The method according to embodiment 15", wherein in the aqueous mixture prepared in step (i), the amount of precursor, calculated as oxide, preferably alumina, silica, zirconia or titania, more preferably the amount of zirconium salt, calculated as ZrO2, is in the range of 1 to 10% by weight, preferably in the range of 2 to 8% by weight, more preferably in the range of 3 to 7% by weight, based on the weight of the zeolitic material contained in the aqueous mixture prepared in step (i).
[0273] 17" The method according to any one of embodiments 7" to 16", wherein 98 to 100% by weight, preferably 99 to 100% by weight, more preferably 99.5 to 100% by weight, more preferably 99.9 to 100% by weight of the aqueous mixture prepared in step (i) consists of water, the copper-containing zeolitic material, and a source of copper other than the copper-containing zeolitic material.
[0274] 18" The method according to any one of embodiments 7" to 16", wherein 98-100% by weight, preferably 99-100% by weight, more preferably 99.5-100% by weight, more preferably 99.9-100% by weight of the aqueous mixture prepared in step (i) consists of water, the copper-containing zeolitic material, a source of copper other than the copper-containing zeolitic material, and a precursor of the acidic component as defined in embodiment 15" or 16".
[0275] 19". Step (i) is (i.1) preparing a first mixture comprising water and a source of copper other than a copper-containing zeolitic material; (i.2) preferably milling the first mixture, more preferably until the particles of the first mixture have a Dv90 in the range of 0.5 to 20 micrometers (Dv90 is determined as described in Reference Example 3), optionally adding a precursor of an acidic component as defined in embodiment 15" or 16", (i.3) preparing a second mixture comprising water and a zeolitic material comprising copper; (i.4) mixing the second mixture obtained in step (i.3) with the first mixture obtained in step (i.1), more preferably in step (i.2); Including, The method according to any one of embodiments 7" to 18".
[0276] 20". The method according to embodiment 19", wherein 90-100% by weight, preferably 95-100% by weight, more preferably 98-100% by weight, of the source of copper other than the copper-containing zeolitic material is present in the mixture prepared in step (i.1) in undissolved state.
[0277] 21". The method according to embodiment 19" or 20", wherein the grinding in step (i.2) is carried out until the particles of the first mixture have a Dv90 in the range of 4 to 15 micrometers, preferably in the range of 6 to 12 micrometers, wherein Dv90 is determined as described in Reference Example 3.
[0278] 22". The method according to any one of embodiments 19" to 21", wherein step (i.4) further comprises milling the mixture obtained in step (i.4), preferably until particles of said mixture have a Dv90 in the range of 0.5 to 20 micrometers, more preferably in the range of 2 to 15 micrometers, more preferably in the range of 2 to 10 micrometers, wherein Dv90 is determined as described in Reference Example 3.
[0279] 23". The method according to any one of embodiments 7" to 22", wherein the drying according to step (ii) is carried out in a gas atmosphere having a temperature in the range from 100 to 200 °C, preferably in the range from 120 to 140 °C, and the gas atmosphere preferably comprises oxygen.
[0280] 24". The method according to any one of embodiments 7" to 23", wherein the drying according to step (ii) is carried out in a gas atmosphere for a duration in the range of 0.25 to 3 hours, preferably in the range of 0.5 to 1.5 hours, and the gas atmosphere preferably comprises oxygen.
[0281] 25". The method according to any one of embodiments 7" to 24", wherein the calcination according to step (iii) is carried out in a gas atmosphere having a temperature in the range of 300 to 900 °C, preferably in the range of 400 to 500 °C, and the gas atmosphere preferably comprises oxygen.
[0282] 26". The method according to any one of embodiments 7" to 25", wherein the calcination according to step (iii) is carried out for a duration in the range of 0.5 to 8 hours, preferably in the range of 1.5 to 3 hours, in a gas atmosphere, the gas atmosphere preferably comprising oxygen.
[0283] 27" The method according to any one of embodiments 7" to 26", wherein the mass ratio of copper (calculated as CuO) contained in the zeolitic material obtained in step (iii) to copper (calculated as CuO) contained in the zeolitic material contained in the mixture from step (i) is in the range of 1.5:1 to 10:1, preferably in the range of 2:1 to 5:1, more preferably in the range of 2:1 to 4:1.
[0284] 28". The method according to any one of embodiments 7" to 27", comprising steps (i), (ii) and (iii).
[0285] 29". A zeolitic material having framework type CHA and comprising copper, obtained or obtainable by a method according to any one of embodiments 7" to 28", preferably a zeolitic material according to any one of embodiments 1" to 6".
[0286] 30". Use of the zeolitic material according to any one of embodiments 1" to 6" and embodiment 29" as a catalyst or as a catalytic article, preferably for the selective catalytic reduction of nitrogen oxides.
[0287] 31". The zeolitic material according to any one of embodiments 1" to 6" and embodiment 29" comprised in a catalyst according to any one of embodiments 44 to 55 according to the first set of embodiments.
[0288] The present invention is further illustrated by the following Reference Examples, Comparative Examples and Examples. EXAMPLES
[0289] Reference Example 1 Measurement of BET specific surface area The BET specific surface area was determined according to DIN 66131 or DIN-ISO 9277 using liquid nitrogen.
[0290] Reference Example 2 Measurement of the average porosity and average pore size of porous wall-flow substrates The average porosity of the porous wall-flow substrates was determined by mercury intrusion using mercury porosimetry according to DIN 66133 and ISO 15901-1.
[0291] Reference Example 3 Determination of volume-based particle size distribution The particle size distribution was determined by static light scattering method using a Sympatec HELOS (3200) & QUIXEL instrument in the range of 6–10% optical density of the samples.
[0292] Reference Example 4: Cu-chabazite prepared according to conventional liquid phase ion exchange (LPIE) method The zeolitic materials having Cu-containing framework-type CHA and used in some of the examples herein were prepared essentially as disclosed in US 8,293,199 B2, see in particular inventive example 2 at column 15, lines 26-52 of US 8,293,199 B2.
[0293] Comparative Example 1: Method for preparing a catalyst containing a copper-containing zeolite material not according to the present invention Slurry 1: Cu-chabazite with a Cu content of 3.4% by mass (calculated as CuO and based on the mass of chabazite) (Dv50 of 20 micrometers, SiO2:Al2O3 molar ratio of 25, primary particle size less than 0.5 micrometers, and BET specific surface area of approximately 600 m 2 / g) was prepared and dispersed in water as described in Reference Example 4. The resulting mixture had a solid content of 40% by weight based on the weight of the mixture. The resulting mixture was milled using a continuous milling device such that the particles of the mixture had a Dv90 value of 5 micrometers.
[0294] Slurry 2: Separately, an aqueous slurry was prepared, which had a solid content of 30% by weight based on the weight of the slurry, and was composed of water and alumina (94% by weight Al2O3, 6% by weight SiO2, and a BET specific surface area of 173 m2). 2 / g, Dv90 of about 5 micrometers). The amount of alumina + silica was calculated so that the amount of alumina + silica after calcination was 10 wt% based on the weight of the calcined chabazite. Tartaric acid was added to the aqueous slurry. The amount of tartaric acid was calculated so that it was 0.7 wt% based on the weight of alumina + silica in the coating after calcination.
[0295] Slurry 1 and slurry 2 were then combined. Acetic acid was added to the resulting slurry. The amount of acetic acid was calculated to be 1 wt% based on the weight of Cu-chabazite. The solid content of the final slurry was adjusted to 34 wt% based on the weight of the slurry.
[0296] A porous uncoated wall-flow filter substrate, silicon carbide (average porosity 63%, average pore size 20 micrometers, 300 CPSI and wall thickness 12 mil, diameter: 165.1 mm) * A 100% axial length substrate (length: 140.5 mm) was coated twice with the final slurry from the inlet end to the outlet end. To do this, the substrate was immersed in the final slurry from the inlet end until the slurry reached the top of the substrate. A pressure pulse was then applied to the inlet end to spread the slurry evenly over the substrate. The coated substrate was then dried at 130°C for 2 hours and calcined at 450°C for 2 hours. This was repeated once. The final coating loading after calcination was 2.0 g / in based on the mass of chabazite. 3 is about 1.76 g / in 3 of chabazite, 0.18 g / in 3 of alumina+silica, and 3.4 wt. % Cu, calculated as CuO.
[0297] Comparative Example 2: Method for preparing a catalyst containing a copper-containing zeolite material not according to the present invention Slurry 1: CuO powder with a Dv50 of 33 micrometers was added to the water. The amount of CuO was calculated so that the total amount of copper in the calcined coating was 3.5% by weight, calculated as CuO, based on the weight of the chabazite. The resulting mixture was milled using a continuous milling device so that the particles had a Dv50 value of about 2.5 micrometers and a Dv90 value of about 9 micrometers. The resulting slurry had a solids content of 5% by weight, based on the weight of the slurry. An aqueous zirconium acetate solution was added to the CuO-containing mixture forming the slurry. The amount of zirconium acetate was calculated so that the amount of zirconia in the coating was 5% by weight, calculated as ZrO2, based on the weight of the chabazite. Separately, H-chabazite (Dv50 of 20 micrometers, SiO2:Al2O3 of 25, primary particle size less than 0.5 micrometers, BET specific surface area of about 600 m 2 / g) was added to water to form a mixture having a solids content of 38% by weight based on the weight of the mixture. H The Cu-chabazite mixture was mixed into the copper-containing slurry. The amount of Cu-chabazite was calculated so that the loading of chabazite after calcination was 84.4% of the loading of the coating on the catalyst after calcination. The resulting slurry was milled using a continuous milling device to obtain particles with a Dv90 value of about 5 micrometers.
[0298] Slurry 2: This slurry was prepared as Slurry 2 in Comparative Example 1.
[0299] Slurry 1 and slurry 2 were then combined. Acetic acid was added to the resulting slurry. The amount of acetic acid was calculated to be 1 wt% based on the weight of chabazite + Cu. The solids content of the final slurry was adjusted to 34 wt% based on the weight of the slurry.
[0300] A porous uncoated wall-flow filter substrate, silicon carbide (average porosity 63%, average pore size 20 micrometers, 300 CPSI and wall thickness 12 mil, diameter: 165.1 mm) *A 100% axial length substrate (length: 140.5 mm) was coated twice with the final slurry from the inlet end to the outlet end. To do this, the substrate was immersed in the final slurry from the inlet end until the slurry reached the top of the substrate. A pressure pulse was then applied to the inlet end to spread the slurry evenly over the substrate. The coated substrate was then dried at 130° C. for 2 hours and calcined at 450° C. for 2 hours.
[0301] This was repeated once. The final coating loading after calcination was 2.0 g / in based on the mass of chabazite. 3 and 1.688g / in 3 of chabazite, 0.0844 of zirconia, 0.1688 of alumina+silica, and 3.5 wt. % Cu, calculated as CuO.
[0302] Example 1: Method for preparing a catalyst comprising copper-containing zeolitic material Slurry 1: CuO powder having a Dv50 of 33 micrometers was added to the water. The amount of CuO was calculated so that the total amount of copper, calculated as CuO, was 3.5% by weight based on the weight of the chabazite in the coating after calcination. The resulting mixture was ground using a continuous grinding device so that the particles had a Dv50 value of about 2.5 micrometers and a Dv90 value of about 9 micrometers. The resulting slurry had a solid content of 5% by weight based on the weight of the slurry. An aqueous zirconium acetate solution was added to the CuO-containing mixture forming the slurry. The amount of zirconium acetate was calculated so that the amount of zirconia, calculated as ZrO2, was 5% by weight based on the weight of the chabazite in the coating. Separately, a Cu-chabazite mixture with a Cu content of 1.30% by mass (calculated as CuO and based on the mass of chabazite) (Dv50 of 20 micrometers, SiO2:Al2O3 molar ratio of 25, primary particle size less than 0.5 micrometers, and BET specific surface area of approximately 600 m2) was prepared. 2 / g) was prepared as described in Reference Example 4 and added to water to form a mixture, which had a solid content of 34% by weight based on the weight of the mixture. The Cu-chabazite mixture was mixed with the copper-containing slurry. The amount of Cu-chabazite was calculated so that the loading of chabazite after calcination was 84.2% of the loading of the coating on the catalyst after calcination. The resulting slurry was milled using a continuous milling device so that the particles had a Dv90 value of about 5 micrometers.
[0303] Slurry 2: Separately, an aqueous slurry was prepared, which had a solid content of 30% by weight based on the weight of the slurry, and was composed of water and alumina (94% by weight Al2O3, 6% by weight SiO2, and a BET specific surface area of 173 m2). 2 / g, Dv90 of about 5 micrometers). The amount of alumina + silica was calculated so that the amount of alumina + silica after calcination was 10 wt% based on the weight of the calcined chabazite. Tartaric acid was added to the aqueous slurry. The amount of tartaric acid was calculated so that it was 0.7 wt% based on the weight of alumina + silica in the coating after calcination.
[0304] Slurry 1 and slurry 2 were then combined. Acetic acid was added to the resulting slurry. The amount of acetic acid was calculated to be 1% by weight based on the weight of the chabazite. The solid content of the final slurry obtained was adjusted to 34% by weight based on the weight of the slurry.
[0305] A porous uncoated wall-flow filter substrate, silicon carbide (average porosity 63%, average pore size 20 micrometers, 300 CPSI and wall thickness 12 mil, diameter: 165.1 mm) *A 100% axial length substrate (length: 140.5 mm) was coated twice with the final slurry from the inlet end to the outlet end. To do this, the substrate was immersed in the final slurry from the inlet end until the slurry reached the top of the substrate. A pressure pulse was then applied to the inlet end to spread the slurry evenly over the substrate. The coated substrate was then dried at 130°C for 2 hours and calcined at 450°C for 2 hours. This was repeated once. The final coating loading after calcination was approximately 2.0 g / in based on the mass of chabazite. 3 and 1.684 g / in 3 of chabazite, 0.1684 g / in 3 of alumina + silica, 0.0842 g / in 3 The zeolitic material contained zirconia and 3.5 wt. % Cu, calculated as CuO. The weight ratio of copper contained in the zeolitic material contained in the coated substrate to the copper contained in the zeolitic material used in slurry 1 (starting zeolitic material), calculated as CuO, was about 2.5:1.
[0306] Example 2: Performance evaluation of catalysts of Example 1 and Comparative Examples 1 and 2 - NOx conversion rate All catalysts were aged in an oven at 800° C. for 16 hours under hydrothermal conditions (10% H2O, 20% O2, and 70% N2). All catalysts were also aged in an oven at 850° C. for 16 hours under hydrothermal conditions (10% H2O, 20% O2, and 70% N2).
[0307] The NOx conversion at 20 ppm NH3 slip of the aged catalysts of Example 1, Comparative Examples 1 and 2 was measured on an engine bench equipped with a Euro 6 150 kW engine (OM651) at various temperatures, i.e., 200, 230, 600 and 650° C. The results are shown in Figure 1 (after hydrothermal aging at 800° C.) and Figure 2 (after hydrothermal aging at 850° C.).
[0308] As clearly shown in Figure 1, the aged catalyst of Example 1 exhibited improved NOx conversion at 200, 230, 600 and 650°C compared to the aged catalyst of Comparative Example 1 comprising a copper-containing zeolitic material prepared by a liquid phase ion exchange method. In particular, the aged catalyst of Example 1 exhibited about 10-12% higher NOx conversion than that obtained with the aged catalyst of Comparative Example 1. Furthermore, the aged catalyst of Example 1 exhibited improved NOx conversion at 200, 230 and 600°C compared to the aged catalyst of Comparative Example 2 comprising a copper-containing zeolitic material prepared by an in-situ ion exchange (ISIE) procedure (but starting from the H-form of the zeolitic material).
[0309] As clearly shown in Figure 2, the aged catalyst of Example 1 exhibited improved NOx conversion at 200, 230, 600 and 650°C compared to the aged catalyst of Comparative Example 1, which contained a copper-containing zeolitic material prepared by a liquid phase ion exchange method. In particular, the aged catalyst of Example 1 exhibited about 10-15% higher NOx conversion than that obtained with the aged catalyst of Comparative Example 1. Furthermore, the aged catalyst of Example 1 exhibited improved NOx conversion at 200, 230, 600 and 650°C compared to the aged catalyst of Comparative Example 2, which contained a copper-containing zeolitic material prepared by an in-situ ion exchange (ISIE) procedure, but starting from the H-form of the zeolitic material.
[0310] Thus, Example 2 shows that the catalyst prepared according to the invention provides improved catalytic activity, especially NOx conversion, under aging conditions. This example thus demonstrates that by using the claimed method for preparing a catalyst comprising a copper-containing zeolitic material, i.e., by using a specific combination of conventional liquid phase ion exchange (LPIE) and in-situ ion exchange (ISIE) procedures according to the invention, it is possible to improve the catalytic activity of said catalyst, as well as its thermal stability.
[0311] Comparative Example 3: Method for preparing a catalyst containing a copper-containing zeolitic material not according to the present invention The catalyst of Comparative Example 3 was prepared like the catalyst of Comparative Example 2, except that the final slurry was coated onto a different substrate, specifically, a porous uncoated wall-flow filter substrate, silicon carbide (average porosity 60.5%, average pore size 20 micrometers, 350 CPSI and wall thickness 0.28 mm, diameter: 172.8 mm). * The coating method was the same. The final coating loading after calcination was 2.2 g / in 3 It was.
[0312] Example 3: Method for preparing a catalyst comprising copper-containing zeolitic material The catalyst of Example 3 was prepared like that of Example 1, except that the final slurry was coated onto a different substrate, specifically, a porous uncoated wall-flow filter substrate, silicon carbide (average porosity 60.5%, average pore size 20 micrometers, 350 CPSI and wall thickness 0.28 mm, diameter: 172.8 mm). * The coating method was the same. The final coating loading after calcination was 2.2 g / in 3 It was.
[0313] Example 4: Backpressure Evaluation The back pressure of the catalysts obtained in Example 3 and Comparative Example 3 was measured using a Superflow 1020 measuring device. Specifically, three lots of the catalyst prepared in Example 3 and three lots of the catalyst prepared in Comparative Example 3 were tested. 3 The backpressure data recorded at volumetric flow rates in 1000 g / h are reported in Table 1 below.
[0314] [Table 1]
[0315] Table 1 shows that the average backpressures measured from the three lots prepared according to Comparative Example 3 were all greater than 60 mbar, and that the backpressure varied widely between these various lots. In contrast, the backpressures measured for the lots prepared according to Example 3 were all less than 50 mbar, with a lot-to-lot variation of less than 5 mbar. Thus, the method that is the subject of the present invention provides a more consistent and lower backpressure than the ISIE method using H-type chabazite as the starting material, with a process that completely exchanges CuO.
[0316] Example 5: Method for preparing a catalyst comprising copper-containing zeolitic material The catalyst of Example 5 was prepared like that of Example 1, except that the amount of CuO was increased to 3.75 wt. % based on the weight of chabazite. The final coating loading after calcination was 2.0 g / in. 3 The mass ratio of copper contained in the zeolitic material contained in the coated substrate to the copper contained in the zeolitic material used in Slurry 1 (starting zeolitic material), calculated as CuO, was about 3:1.
[0317] Example 6: Method for preparing a catalyst containing a copper-containing zeolitic material not according to the present invention The catalyst of Example 6 was prepared like that of Example 5, except that no zirconium acetate was added to Slurry 1. The final coating loading after calcination was 2.0 g / in 3 It was.
[0318] Example 7: Performance test of the catalysts of Examples 5 and 6 - NOx conversion and NH3 storage capacity The catalysts were aged in an oven at 800° C. for 16 hours under hydrothermal conditions (20% O2, 10% H2O, and 70% N2). The NOx conversion at 20 ppm NH3 slip of the aged catalysts of Examples 5 and 6 was measured at various temperatures, i.e., 200, 230, and 680° C., in a 21140 kW Euro 6 (EDC17-ETK SG) engine. The results are shown in FIG. 3.
[0319] All catalysts were also aged in an oven at 850° C. for 16 hours under hydrothermal conditions (10% H2O, 20% O2 and 70% N2). The NOx conversion at 20 ppm NH3 slip of the aged catalysts of Examples 5 and 6 was measured at various temperatures, i.e., 200 and 230, in a 21140 kW Euro6 (EDC17-ETK SG) engine. The results are shown in FIG. 4.
[0320] The ammonia storage capacity of the aged catalysts of Examples 5 and 6 was measured at different temperatures, i.e., 200 and 230°C, after the NOx conversion measurements and after urea injection was stopped. Specifically, the measured ammonia storage capacity (ammonia stored in the catalyst) corresponds to the total amount of reaction of NOx and NH3 that still leaves the catalyst after urea injection is stopped. The results are shown in Figure 5.
[0321] Figures 3 to 5 show that the catalysts of Examples 5 and 6 exhibit comparable catalytic performance at various temperatures, i.e., 200, 230 and 680° C. Thus, Example 7 clearly demonstrates that the use of the precursor of the acidic component, i.e., zirconium acetate, in preparing a catalyst slurry containing copper-containing zeolitic material is not relevant for performance under the test conditions compared to the performance of the examples of the present application.
[0322] Comparative Example 4: Preparation of a zeolitic material having framework type CHA and containing copper, not according to the invention Slurry 1 and slurry 2 were prepared as in Comparative Example 1. Slurry 1 and slurry 2 were then combined. Acetic acid was added to the resulting slurry. The amount of acetic acid was calculated to be 1 wt% based on the weight of chabazite. The resulting slurry was then dried at 130°C for 1 hour and calcined at 450°C for 2 hours to obtain a powder containing 87.4 wt% of a zeolite material having a framework type CHA and containing copper, 4.3 wt% of zirconia, and 8.4 wt% of a mixture of alumina and silica.
[0323] Example 8: Preparation of zeolitic material with framework type CHA and containing copper The preparation of slurry 1 and slurry 2 was carried out as in Example 1, except that the amount of chabazite in slurry 1 was calculated so that the amount of chabazite in the final powder after calcination was 87.2% by weight based on the weight of the powder, and the amount of alumina + silica was calculated so that the amount of alumina + silica after calcination was 8.5% by weight based on the weight of the powder. Slurry 1 and slurry 2 were then combined. Acetic acid was added to the resulting slurry. The amount of acetic acid was calculated so that it was 1% by weight based on the weight of the chabazite. The resulting slurry was further dried at 130°C for 1 hour and calcined at 450°C for 2 hours to obtain a powder containing 87.2% by weight of a zeolitic material having a framework type CHA and containing copper, 4.3% by weight of zirconia, and 8.5% by weight of a mixture of alumina and silica.
[0324] Comparative Example 5: Preparation of a zeolitic material having framework type CHA and containing copper, not according to the invention The zeolitic material of Comparative Example 5 was prepared like the zeolitic material of Example 8, except that the amount of copper after calcination was calculated to be 3.17 wt. % CuO based on the weight of chabazite, and no calcination was performed after drying at 130° C. for 1 hour.
[0325] Example 9: Preparation of zeolitic material with framework type CHA and containing copper The zeolitic material of Example 9 was prepared like the zeolitic material of Comparative Example 5, except that the calcination step was carried out at 450° C. for 2 hours after drying at 130° C. for 1 hour.
[0326] Example 10: Preparation of zeolitic material with framework type CHA and containing copper The zeolitic material of Example 10 was prepared as in Example 8, except that the amount of CuO was calculated so that the total amount of copper after calcination was 3.31 wt. %, calculated as CuO based on the weight of the chabazite, and zirconium acetate was not used.
[0327] Example 11: Ammonia back exchange (BEX) experiments Ammonia back-exchange (BEX) experiments were performed on the calcined zeolitic materials of Examples 8, 9 and 10, the calcined zeolitic material of Comparative Example 4, and the dried zeolitic material of Comparative Example 5. BEX experiments were also performed on the starting material of Example 8 (Cu-chabazite with a Cu content of 1.30 wt. % calculated as CuO based on the mass of chabazite). In the BEX experiment, the exchanged Cu in the zeolitic material is removed and the remaining Cu is unexchanged CuO. The amount of residual Cu was determined by ICP and the delta of the amount of Cu before and after ammonia back-exchange is the amount of exchanged Cu. The results are shown in Table 2 below.
[0328] [Table 2]
[0329] * Calculated as CuO based on the mass of the zeolite material
[0330] Example 6 shows that the amount of exchanged copper in the zeolite materials of Example 8 and Comparative Example 4 is approximately the same.
[0331] Example 12: Diffuse Reflectance Infrared Fourier Transform Spectroscopy (DRIFTS) Measurement Diffuse reflectance infrared Fourier transform spectroscopy (DRIFTS) measurements were performed using a THERMO NICOLET equipped with an MCT (HgCdTe) detector and a Harrick environmental chamber equipped with ZnSe windows. The zeolite materials of Comparative Examples 4 and 5, Examples 8-10, and the starting zeolite material of Example 8 were ground to fine powder in a mortar and pestle and placed in a sample cup. The powder was dehydrated at 400 °C for 1 h in Ar flowing at 40 mL / min and cooled to 30 °C, after which a spectrum was recorded using KBr as a reference. The copper species in the zeolite material can be identified by infrared (IR) spectroscopy by monitoring the vibrations of the disordered TOT bonds (Si-O-Al and Si-O-Si). The structural vibrations of the TOT bonds in the zeolite range from 1300 to 1000 cm in the asymmetric vibrational mode. -1 , and 850 to 750 cm for symmetric vibration mode.-1 The asymmetric TOT vibrational frequency of the oxygen ring is sensitive to the interaction with cations, so that upon interaction with cations, the IR bands are typically at 1000–1300 cm -1 (characteristic position for undisordered rings) from about 850-1000 cm -1 The shifted band appears in the transmission window between the two strong bands of the TOT asymmetric and symmetric vibrations. The position of such shifted band depends on the properties of the cation. Such disordered vibration of TOT bond is observed due to the strong interaction between the copper ion and the neighboring oxygen atoms in the framework when the copper ion is exchanged into the cationic sites of the zeolite framework. The peak position depends on the state of the compensated cation and the structure of the zeolite framework. The peak intensity depends on the amount of the compensating cation in the exchange site. Figure 6 shows the DRIFTS of the TOT bond.
[0332] Peak fitting was performed with Origin 9.1 software. In peak fitting, the peaks were modeled as Gaussian peaks, and peak fitting runs were performed until the chi-square tolerance reached 1E-6. The 900–955 cm band, which is due to the vibrational absorption of the disordered TOT bond, was eliminated. -1 The IR signal in the wavelength range of 900 cm was attributed to the exchanged copper ions in the zeolite material. -1 The absorption peak with a maximum at the wavelength of Cu 2+ This is due to the vibration of the disordered TOT bond caused by -1 The absorption peak with a maximum at the wavelength of Cu(OH) + The results were attributed to the disordered vibration of the TOT bond due to the ion beam. To enable the software to deconvolute the peaks, a wavelength of 935 cm was used. -1 Peak positions of 955~900cm are included. -1 The total peak area of CuOH + and Cu 2+ The results are shown in Table 3 below.
[0333] [Table 3]
[0334] * 955~900cm -1 All absorption peaks with a maximum value in the range
[0335] As shown in Table 3, the IR spectrum of the zeolite material of Example 8 shows a peak at about 955 cm, as can be seen from Figures 6, 7 and Table 3. -1 The first absorption peak (P1) has a maximum at about 900 cm -1 The peak area of the first absorption peak (P1) was 900 to 955 cm. The ratio of the peak area of the first absorption peak to the peak area of the second absorption peak, P1:P2, was 1.178:1 (=66:56). The peak area of the first absorption peak (P1) was 900 to 955 cm. -1 The peak area of the second absorption peak (P2) was 43.42% of the total peak area of all absorption peaks with a maximum in the range of 900–955 cm. -1 These disordered signals are due to the absorption of vibrations of the TOT bond by the exchanged copper ions. Cu(OH) accounted for 36.84% of the total peak area of all absorption peaks with maxima in the range of 1000 to 15000. These disordered signals are due to the absorption of vibrations of the TOT bond by the exchanged copper ions. Cu(OH) + It is believed that 43.42% of the total exchanged copper ions in the zeolite material of Example 8 were Cu 2+ It is believed that this was the case.
[0336] The IR signal of the zeolite material of Comparative Example 4 is approximately 955 cm as can be seen from FIG. 5 and Table 3. -1 The first absorption peak (P1) has a maximum at about 900 cm -1The ratio of the peak area of the first absorption peak to the peak area of the second absorption peak, P1:P2, was 1.65:1 (=91:55). The peak area of the first absorption peak (P1) was in the range of 900 to 955 cm -1 The peak area of the second absorption peak (P2) was 59.1% of the total peak area of all absorption peaks with a maximum in the range of 900–955 cm. -1 These disordered signals are due to the absorption of vibrations of the TOT bond by the exchanged copper ions. Cu(OH) accounted for 35.7% of the total peak area of all absorption peaks with maxima in the range of 1000 to 15000. These disordered signals are due to the absorption of vibrations of the TOT bond by the exchanged copper ions. Cu(OH) + It is believed that 59.1% of the total exchanged copper ions in the zeolite material of Comparative Example 4 was Cu 2+ It is believed that this was the case.
[0337] The IR spectrum of the zeolite material of Example 9 shows a peak at about 955 cm as can be seen from FIG. 6 and Table 3. -1 The first absorption peak (P1) has a maximum at about 900 cm -1 The IR spectrum of the zeolite material of Example 10 includes a second absorption peak (P2) having a maximum at about 955 cm. The ratio of the peak area of the first absorption peak to the peak area of the second absorption peak, P1:P2, was 1.276:1 (=60:47). As can be seen from FIG. 6 and Table 3, the IR spectrum of the zeolite material of Example 10 includes a second absorption peak (P2) having a maximum at about 955 cm. -1 The first absorption peak (P1) has a maximum at about 900 cm -1 The ratio of the peak area of the first absorption peak to the peak area of the second absorption peak, P1:P2, was 1.264:1 (=67:53).
[0338] Comparative Example 6: Preparation of a catalyst containing a copper-containing zeolitic material not according to the invention Slurry 1: CuO powder with a Dv50 of 33 micrometers was added to water. The amount of CuO was calculated so that the total amount of copper, calculated as CuO, was 4.15% by weight based on the weight of chabazite in the coating after calcination. The resulting mixture was milled using a continuous milling device so that the particles had a Dv50 value of about 2.5 micrometers and a Dv90 value of about 9 micrometers. The resulting slurry had a solid content of 5% by weight based on the weight of the slurry. An aqueous zirconium acetate solution was added to the CuO-containing mixture forming the slurry. The amount of zirconium acetate was calculated so that the amount of zirconia, calculated as ZrO2, was 5% by weight based on the weight of chabazite in the coating. Separately, H-type-chabazite (Dv50 of 13 micrometers, SiO2:Al2O3 of 18, average crystal size less than 0.5 micrometers (SEM analysis) and BET specific surface area of about 560 m2) was obtained. 2 H-chabazite mixture was mixed with the copper-containing slurry. The amount of chabazite was calculated such that the loading of chabazite after calcination was about 85% of the loading of the coating on the catalyst after calcination. The resulting slurry was milled using a continuous milling device such that the particles had a Dv90 value of about 5 micrometers.
[0339] Slurry 2: Separately, an aqueous slurry was prepared, which had a solid content of 30% by weight based on the weight of the slurry, and was composed of water and alumina (94% by weight Al2O3, 6% by weight SiO2, and a BET specific surface area of 173 m2). 2 / g, Dv90 of about 18 micrometers. The amount of alumina + silica was calculated so that the amount of alumina + silica after calcination was 10 wt% based on the weight of the calcined chabazite. Tartaric acid was added to the aqueous slurry.
[0340] Slurry 1 and Slurry 2 were then combined to form an intermediate slurry.
[0341] Additionally, synthetic graphite powder (Dv50 6.2 micrometers, Dv90 12.5 micrometers) was separately dispersed in deionized water for 30 minutes to form an aqueous slurry with a solid content of 35% by weight. The amount of synthetic graphite was calculated to be 10% by weight based on the weight of the starting chabazite + alumina-silica. This mixture was added to the intermediate slurry.
[0342] Acetic acid was added to the resulting slurry. The amount of acetic acid was calculated to be 1.7% by weight based on the weight of the chabazite. The solid content of the resulting final slurry was adjusted to 37% by weight based on the weight of the slurry.
[0343] A porous uncoated wall-flow filter substrate, silicon carbide (average porosity 60.5%, average pore size 20 micrometers, 350 CPSI and wall thickness 0.30 mm (13 mil), diameter: 58 mm * A 100% axial length substrate (length: 150.5 mm) was coated twice with the final slurry from the inlet end to the outlet end. To do this, the substrate was immersed in the final slurry from the inlet end until the slurry reached the top of the substrate. A pressure pulse was then applied to the inlet end to spread the slurry evenly over the substrate. The coated substrate was then dried at 140°C for 30 minutes and calcined at 450°C for 2 hours. This was followed by calcination at 800°C for 30 minutes. This was repeated once. The final coating loading after calcination was approximately 2.0 g / in based on the mass of chabazite. 3 is about 1.7 g / in 3 of chabazite, 0.17 g / in 3 of alumina + silica, approximately 0.085 g / in 3 % zirconia, and 4.15 wt. % Cu, calculated as CuO. The weight ratio of copper in the zeolitic material in the coated substrate to copper in the zeolitic material used in slurry 1 (starting zeolitic material), calculated as CuO, was about 1:0.
[0344] Example 13: Preparation of catalyst containing copper-containing zeolitic material The catalysts of Examples 13.1, 13.2 and 13.3 were prepared as in Comparative Example 6, except that pre-exchanged Cu-CHA was used instead of H-form-CHA in Slurry 1 (see Table 4 below). Pre-exchanged Cu-CHA was prepared as in Reference Example 4.
[0345] [Table 4]
[0346] * % by weight calculated as CuO based on the weight of the zeolite material ** Cu(c): Cu content in the coated substrate / Cu(s): Cu content in the starting zeolite material
[0347] Example 14: Performance evaluation of catalysts of Comparative Example 6 and Examples 13.1 to 13.3 - NO x Conversion and Backpressure All catalysts were aged in an aging oven at 800° C. under hydrothermal conditions (10% H2O, 20% O2 and 70% N2) for 16 hours.
[0348] Maximum NO for the aged catalysts of Comparative Example 6 and Examples 13.1 to 13.3 x The conversion was measured at steady-state conditions on an engine bench equipped with a Euro 6 140 kW engine (2.0 L, 4 cylinders) at various temperatures, namely 216, 235 and 635° C. The results are shown in FIG.
[0349] As can be seen from FIG. 8, the aged catalysts of Examples 13.1-13.3 showed improved NO at 216° C. and 235° C. compared to the aged catalyst of Comparative Example 6, which was prepared only by in-situ ion exchange (ISIE) starting from the H-form of the zeolite material. x In particular, the aged catalyst of Example 13.3 showed approximately 7% higher NO conversion than that obtained with the aged catalyst of the comparative example using starting materials that were not pre-exchanged.x FIG. 9 shows the correlation between pre-loaded copper using liquid phase ion exchange and NOx conversion. Furthermore, the aged catalyst of Example 13.2 showed improved NOx conversion even at 635° C. compared to the aged catalyst of Comparative Example 6. x The conversion was shown.
[0350] Thus, it has been demonstrated that the catalyst prepared according to the present invention provides improved catalytic activity under aging conditions. Thus, this example demonstrates that by using the method of the present invention to prepare a catalyst comprising a copper-containing zeolitic material, i.e., by using a specific in-situ ion exchange (ISIE) method on a pre-exchanged zeolitic material, it is possible to improve the catalytic activity of said catalyst and its thermal stability.
[0351] Furthermore, the back pressure of the catalysts obtained in Comparative Example 6 and Examples 13.1 to 13.3 was measured using a measuring device designed by our company. 3 The backpressure data recorded at volumetric flow rates in 1000 g / h are reported in Table 5 below.
[0352] [Table 5]
[0353] Comparative Example 7: Preparation of a catalyst containing a copper-containing zeolitic material not according to the invention Slurry 1: CuO powder with a Dv50 of 33 micrometers was added to water. The amount of CuO was calculated so that the total amount of copper, calculated as CuO, was 4.34 wt.% based on the weight of chabazite in the coating after calcination. The resulting mixture was ground using a continuous grinding device so that the particles had a Dv90 value of about 5.5 micrometers. The resulting slurry had a solid content of 5 wt.% based on the weight of the slurry. An aqueous zirconium acetate solution was added to the CuO-containing mixture forming a slurry. The amount of zirconium acetate was calculated so that the amount of zirconia, calculated as ZrO2, was 5 wt.% based on the weight of chabazite in the coating. Separately, H-type-chabazite (Dv50 of 13 micrometers, SiO2:Al2O3 of 18, average crystal size less than 0.5 micrometers (SEM analysis) and BET specific surface area of about 560 m2) was obtained. 2 H-chabazite mixture was mixed with the copper-containing slurry. The amount of chabazite was calculated such that the loading of chabazite after calcination was about 85% of the loading of the coating on the catalyst after calcination. The resulting slurry was milled using a continuous milling device such that the particles had a Dv90 value of about 5 micrometers.
[0354] Slurry 2: Separately, an aqueous slurry was prepared, which had a solid content of 30% by weight based on the weight of the slurry, and was composed of water and alumina (94% by weight Al2O3, 6% by weight SiO2, and a BET specific surface area of 173 m2). 2 / g, Dv90 of about 18 micrometers. The amount of alumina + silica was calculated so that the amount of alumina + silica after calcination was 10 wt. % based on the weight of the calcined chabazite.
[0355] Slurry 1 and slurry 2 were then combined. Acetic acid was added to the resulting slurry. The amount of acetic acid was calculated to be 1.7% by weight based on the weight of the chabazite. The solids content of the resulting final slurry was adjusted to 32% by weight based on the weight of the slurry.
[0356] A porous uncoated wall-flow filter substrate, silicon carbide (average porosity 60.5%, average pore size 20 micrometers, 350 CPSI, and wall thickness 0.33 mm (13 mil), diameter: 58 mm * A 100% axial length substrate (length: 150.5 mm) was coated twice with the final slurry from the inlet end to the outlet end. To do this, the substrate was immersed in the final slurry from the inlet end until the slurry reached the top of the substrate. A pressure pulse was then applied to the inlet end to spread the slurry evenly over the substrate. The coated substrate was then dried at 140°C for 30 minutes and calcined at 450°C for 1 hour. This was repeated once. The final coating loading after calcination was approximately 2.0 g / in based on the mass of chabazite. 3 is about 1.7 g / in 3 of chabazite, 0.17 g / in 3 of alumina + silica, approximately 0.085 g / in 3 % zirconia, and 4.34 wt. % Cu, calculated as CuO. The mass ratio of copper in the zeolitic material in the coated substrate to copper in the zeolitic material used in slurry 1 (starting zeolitic material), calculated as CuO, was about 1:0.
[0357] Comparative Example 8: Preparation of a catalyst comprising a copper-containing zeolitic material not according to the invention The catalyst of Comparative Example 8 was prepared like the catalyst of Comparative Example 7, except that the zeolite starting material was NH4-CHA used in Slurry 1 instead of H-CHA.
[0358] Comparative Example 9: Preparation of a catalyst containing a copper-containing zeolitic material not according to the invention The catalyst of Comparative Example 9 was prepared as for the catalyst of Comparative Example 7, except that Slurry 1 was prepared as follows.
[0359] Slurry 1: The zirconium acetate solution was dissolved in water and mixed with Cu-CHA zeolite material (Dv50 of 13 micrometers, SiO2:Al2O3 of 18, average crystal size of less than 0.5 micrometers (SEM analysis) and BET specific surface area of approximately 560 m2). 2 / g) (the Cu-CHA zeolite material was prepared as in Reference Example 4 (LPIE)) in water to form a mixture having a solid content of 37% by weight based on the weight of the mixture. The amount of zirconium acetate was calculated such that the amount of zirconia in the coating was 5% by weight, calculated as ZrO2, based on the weight of chabazite. The amount of chabazite was calculated such that the loading of chabazite after calcination was about 85% of the loading of the coating in the calcined catalyst. The resulting slurry was milled using a continuous milling device such that the particles had a Dv90 value of about 5 micrometers.
[0360] Example 15: Preparation of catalyst containing copper-containing zeolitic material The catalysts of Examples 15.1 and 15.2 were prepared as in Comparative Example 7, except that pre-exchanged Cu-CHA was used instead of H-form-CHA in Slurry 1 (see Table 6 below). Pre-exchanged Cu-CHA was prepared as in Reference Example 4.
[0361] [Table 6]
[0362] * % by weight calculated as CuO based on the weight of the zeolite material ** Cu(c): Cu content in coated substrate / Cu(s): starting zeolite
[0363] Cu content in material Example 16: Performance evaluation of catalysts of Comparative Examples 7 to 9 and Example 15 - NO x Conversion rate All catalysts were aged in an aging oven at 800° C. under hydrothermal conditions (10% H2O, 20% O2 and 70% N2) for 16 hours.
[0364] Maximum NO for the aged catalysts of Comparative Examples 7 to 9 and Example 15 x The conversion was measured at steady state conditions on an engine bench equipped with a Euro 6 140 kW engine (2.0 L, 4 cylinders) at different temperatures, namely 208 and 238° C. The results are shown in FIG.
[0365] As can be seen from FIG. 10, the aged catalyst of Example 15.1 exhibited improved NO production at 238° C. compared to the aged catalysts of Comparative Examples 7-9. x The conversion of the aged catalysts of Examples 15.1 and 15.2 was higher than that obtained with the aged catalysts of the Comparative Examples, confirming the improved behavior of using copper pre-exchanged (LPIE) zeolite materials. Further increase in copper content by LPIE results in a drop in activity, as shown in Comparative Example 9. The aged catalysts of Examples 15.1 and 15.2 showed higher NO 2 conversion than that obtained with the aged catalysts of the Comparative Examples. x Conversion is shown at 208°C.
[0366] Thus, Example 16 demonstrates that the catalyst prepared according to the present invention provides improved catalytic activity. Thus, this example demonstrates that by using the claimed method for preparing a catalyst comprising a copper-containing zeolitic material, i.e., by using a specific in-situ ion exchange method, it is possible to improve the catalytic activity of said catalyst, as well as its thermal stability.
[0367] BRIEF DESCRIPTION OF THE DRAWINGS FIG. 1 shows the NOx conversion of aged (hydrothermal aging at 800° C.) Example 1, Comparative Examples 1 and 2 catalysts at various temperatures, namely 200, 230, 600 and 650° C., at 20 ppm NH3 slip.
[0368] FIG. 2 shows the NOx conversion of aged (hydrothermal aging at 850° C.) Example 1, Comparative Examples 1 and 2 catalysts at various temperatures, namely 200, 230, 600 and 650° C., at 20 ppm NH3 slip.
[0369] FIG. 3 shows the NOx conversion of the aged catalysts of Examples 5 and 6 at various temperatures, namely 200, 230 and 680° C.
[0370] FIG. 4 shows the NOx conversion of the aged catalysts of Examples 5 and 6 at various temperatures, namely 200 and 230° C., with 20 ppm NH3 slip.
[0371] FIG. 5 shows the ammonia storage capacity of the aged catalysts of Examples 5 and 6 at various temperatures, namely 200 and 230° C.
[0372] FIG. 6 shows the TOT-bound DRIFTS of Example 8, the starting material of Example 8, and Comparative Example 4.
[0373] FIG. 7 shows a peak fitting analysis (deconvolution diagram) using the peak areas under the first absorption peak and under the second absorption peak of Example 8.
[0374] FIG. 8 shows the maximum NOx conversion at various temperatures, ie, 213, 235, and 635° C., for aged (hydrothermal aging at 800° C.) catalysts of Comparative Example 6 and Examples 13.1-13.3.
[0375] FIG. 9 shows the NOx conversion at 235° C. for aged (hydrothermal aged at 800° C.) catalysts of Comparative Example 6 and Examples 13.1-13.3 with various CuO contents (added via the liquid phase ion exchange process), i.e., 0% (Comparative Example 6), 1.13%, 1.75% and 2.38% CuO versus a constant total CuO loading (4.15%).
[0376] FIG. 10 shows the maximum NOx conversion for the aged (hydrothermally aged at 800° C.) Example 2 catalyst at various temperatures, ie, 208 and 238° C.
[0377] References - WO2018 / 101718A1 - US8,293,199B2
Claims
1. (i) water, zeolite material containing copper; a source of copper other than said copper-containing zeolitic material; and Non-zeolitic acidic materials of mixtures of alumina and silica. preparing an aqueous mixture comprising: (ii) disposing the mixture from step (i) on a surface of an inner wall of a substrate having an inlet end, an outlet end, a substrate axial length extending from said inlet end to said outlet end, and a plurality of passages extending through said substrate and defined by said inner wall; (iii) calcining the substrate obtained in step (ii). Including, The copper-containing zeolitic material contained in the aqueous mixture prepared in step (i) has a framework type CHA, the source of copper other than the copper-containing zeolitic material contained in the aqueous mixture prepared in step (i) is copper oxide; the aqueous mixture prepared in step (i) further comprises a precursor of an acidic component, said precursor being zirconium acetate; A method for producing a NOx conversion catalyst comprising a copper-containing zeolitic material.
2. 2. The method of claim 1, wherein 95 to 100% by weight of the framework structure of the zeolitic material is composed of Si, Al and O.
3. In the framework structure of the copper-containing zeolitic material contained in the aqueous mixture prepared in step (i), the molar ratio of Si to Al is 2 :Al 2 O 3 3. The method of claim 1, wherein the ratio of the ratio of the ration to the total ratio of the ration is in the range of 2:1 to 50:1, calculated as
4. 4. The method according to claim 1, wherein the amount of copper (calculated as CuO) contained in the zeolitic material contained in the aqueous mixture prepared in step (i) is in the range of 0.1 to 3% by weight, based on the weight of the zeolitic material contained in the aqueous mixture prepared in step (i).
5. 5. A process according to any one of claims 1 to 4, wherein the non-zeolitic acidic material contained in the aqueous mixture prepared in step (i) is a mixture of alumina and silica, wherein from 80 to 99% by weight of the mixture of alumina and silica consists of alumina, and from 1 to 20% by weight of the mixture of alumina and silica consists of silica.
6. 6. A method according to any one of claims 1 to 5, wherein the aqueous mixture prepared in step (i) comprises the non-zeolitic acidic material in an amount in the range of 2 to 20% by weight, based on the weight of the zeolitic material contained in the aqueous mixture prepared in step (i).
7. 7. The method according to any one of claims 1 to 6, wherein in the aqueous mixture prepared in step (i), 10 to 90% by weight of said aqueous mixture consists of water.
8. 8. A method according to any one of claims 1 to 7, wherein the amount of said precursor, calculated as zirconia, in the aqueous mixture prepared in step (i) is in the range of 1 to 10% by weight, based on the weight of the zeolitic material contained in the aqueous mixture prepared in step (i).
9. 9. The method of any one of claims 1 to 8, wherein the aqueous mixture prepared in step (i) further comprises one or more acids.
10. Step (i) is (i.1) preparing a first mixture comprising water and a source of copper other than the copper-containing zeolitic material; (i.3) adding a precursor of the acidic component as defined in claim 1 to the first mixture obtained by step (i.1), (i.4) preparing a second mixture comprising water and the copper-containing zeolitic material; (i.5) mixing the second mixture obtained in step (i.4) with the first mixture obtained in step (i.3) to obtain a third mixture; (i.6) preparing a fourth mixture comprising water and the non-zeolitic acidic material, the non-zeolitic acidic material being a mixture of alumina and silica; (i.7) mixing the fourth mixture obtained in step (i.6) with the third mixture obtained in step (i.5); 10. The method of claim 1 , comprising:
11. An aqueous mixture for use in preparing a NOx conversion catalyst, comprising: Water, a zeolite material containing copper; a source of copper other than said copper-containing zeolitic material; and a non-zeolitic acidic material of a mixture of alumina and silica; 10 to 90% by weight of the aqueous mixture is water; the copper-containing zeolitic material has a framework type CHA, and the amount of copper contained in the zeolitic material (calculated as CuO) is in the range of 0.1 to 3 wt. % based on the weight of the zeolitic material; the source of copper other than the copper-containing zeolitic material is copper oxide, and the aqueous mixture comprises the source of copper other than the copper-containing zeolitic material (calculated as CuO) in an amount in the range of 1 to 10% by weight, based on the weight of the zeolitic material; the aqueous mixture comprising the non-zeolitic acidic material in an amount ranging from 2 to 20% by weight, based on the weight of the zeolitic material; the aqueous mixture further comprises a precursor of an acidic component, the precursor being zirconium acetate; in the aqueous mixture, the amount of the precursor, calculated as zirconia, is in the range of 1 to 10% by weight, based on the weight of the zeolitic material; An aqueous mixture used to prepare a catalyst for NOx conversion.
12. 12. The mixture of claim 11, wherein the amount of copper (calculated as CuO) contained in the zeolitic material is in the range of 0.2 to 2% by weight, based on the weight of the zeolitic material.
13. 13. The mixture of claim 11 or 12, wherein the aqueous mixture comprises a source of copper other than the copper-containing zeolitic material (calculated as CuO) in an amount in the range of 1.5 to 5% by weight, based on the weight of the zeolitic material.
14. 14. The mixture of any one of claims 11 to 13, wherein the aqueous mixture comprises a source of copper other than the copper-containing zeolitic material (calculated as CuO) in an amount in the range of 1.5 to 4% by weight, based on the weight of the zeolitic material.
15. 15. The mixture of any one of claims 11 to 14, wherein the aqueous mixture comprises the non-zeolitic acidic material in an amount in the range of 5 to 15% by weight, based on the weight of the zeolitic material.
16. The mixture according to any one of claims 11 to 15, wherein the aqueous mixture comprises 55 to 80% by weight of water.
17. 17. The mixture of any one of claims 11 to 16, further comprising one or more acids.
Citation Information
Patent Citations
Method for preparing novel high-activity SCR catalyst
CN105289708A
Copper CHA zeolite catalysts
JP2010519038A
Process for preparation of copper containing molecular sieves with the CHA structure, catalysts, systems and methods
US8293199B2
Integrated SCR and ammonia oxidation catalyst systems
WO2017037006A1
Ion-exchanged molecular sieve catalyst exhibiting reduced n2o emissions
WO2017153894A1
